Lithium ion secondary battery, preparation method thereof and electric device

By using optimized first artificial graphite and second artificial graphite in the negative electrode sheet of lithium-ion secondary battery, the problem that lithium-ion secondary battery is difficult to take into account high energy density, storage performance and dynamic performance is achieved, and better battery performance is achieved.

CN119833724APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510174727.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries are difficult to take into account high energy density, storage performance and kinetic performance.

Method used

By providing the first negative electrode active material layer and the second negative electrode active material layer in the negative electrode sheet, the first artificial graphite and the second artificial graphite are respectively used to optimize their volume particle size distribution and surface defect degree to form a suitable pore structure and improve ion transport efficiency.

Benefits of technology

The lithium-ion secondary battery is achieved to take into account high energy density, storage performance and dynamic performance, and improve the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833724A_ABST
    Figure CN119833724A_ABST
Patent Text Reader

Abstract

The lithium ion secondary battery comprises a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and negative electrode active material layers, the negative electrode active material layers comprise a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer is located between the negative electrode current collector and the second negative electrode active material layer, and the second negative electrode active material layer is located between the first negative electrode active material layer and the second negative electrode active material layer. The first negative electrode active material layer comprises first artificial graphite, the first artificial graphite comprises primary particles, and Dv501 of the first artificial graphite meets the condition that Dv501 is larger than or equal to 13 microns and smaller than or equal to 18 microns; the R1 of the first artificial graphite satisfies 0 lt; r1 < = 0.14; the second negative electrode active material layer comprises second artificial graphite; the second artificial graphite comprises secondary particles, and the Dv502 of the second artificial graphite meets the condition that Dv502 is more than or equal to 10 microns and less than or equal to 15.5 microns; and R2 of the second artificial graphite is more than or equal to 0.12 and less than or equal to 0.25, so that the lithium ion secondary battery has high energy density, storage performance and dynamic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of batteries, and more specifically, to a lithium-ion secondary battery, a preparation method thereof, and an electrical device using the same. Background Art

[0002] With the increasing environmental pollution, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development.

[0003] The development of battery technology needs to consider various design factors, such as energy density, cycle life, storage performance, charge and discharge rate, reliability, etc. The design of the negative electrode plate is crucial for the performance of the lithium-ion secondary battery. Among them, the negative electrode active material in the negative electrode plate directly affects the storage performance, kinetic performance, and energy density of the lithium-ion secondary battery. Therefore, how to provide a lithium-ion secondary battery that takes into account storage performance, kinetic performance, and high energy density is an urgent technical problem to be solved. Summary of the Invention

[0004] The present application is made in view of the above problems, and its purpose is to provide a lithium-ion secondary battery, a preparation method thereof, and an electrical device using the same, which can make the lithium-ion secondary battery take into account high energy density, storage performance, and kinetic performance.

[0005] In a first aspect, a lithium-ion secondary battery is provided, including a negative electrode plate, the negative electrode plate includes a negative electrode active material layer, the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer is located between the negative electrode current collector and the second negative electrode active material layer, wherein the first negative electrode active material layer includes a first artificial graphite, the first artificial graphite includes primary particles, and the volume particle size distribution Dv501 of the first artificial graphite satisfies: 13 μm ≤ Dv501 ≤ 18 μm; the R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14; wherein, R = I D1 / I G1 where I D1 is the intensity of the D peak, which is the maximum peak intensity in the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the first artificial graphite, and I G1 is the intensity of the G peak, which is the maximum peak intensity in the range of 1535 cm -1 -1635 cm -1The maximum peak intensity within the range is the intensity of the G peak; the second negative electrode active material layer includes a second artificial graphite; the second artificial graphite includes secondary particles, and the volume particle size distribution Dv502 of the second artificial graphite satisfies: 10μm≤Dv502≤15.5μm; R2 of the second artificial graphite satisfies: 0.12≤R2≤0.25; wherein R2=I D2 / I G2 , I D2 The Raman spectrum of the second artificial graphite is 1300 cm -1 -1400cm -1 The maximum peak intensity within the range is the intensity of the D peak, I G2 The Raman spectrum of the second artificial graphite is 1535cm -1 -1635cm -1 The maximum peak intensity within the range is the intensity of the G peak.

[0006] In an embodiment of the present application, by setting the first negative electrode active material layer to include first artificial graphite, the first artificial graphite includes primary particles, and the surface defect degree of the primary particles is relatively low, which is beneficial to reducing the surface defect degree of the first artificial graphite; the volume particle size distribution Dv501 of the first artificial graphite satisfies 13 μm ≤ Dv501 ≤ 18 μm. When Dv501 ≥ 13 μm, the volume particle size distribution Dv501 of the first artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the material crushing process, and thus is beneficial to improving the storage performance of the first negative electrode active material layer; when Dv501 ≤ 18 μm, the risk of reduction in the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the first artificial graphite can be reduced, and the energy density of the first negative electrode active material layer can be improved; R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14, the first artificial graphite has good integrity and uniformity, and the surface defect degree is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the first negative electrode active material layer, and thus is beneficial to the lithium-ion secondary battery to take into account high energy density and storage performance; by setting the second negative electrode active material layer to include second artificial graphite, the second artificial graphite includes secondary particles, and the isotropy of the secondary particles is relatively high, which can improve the ion transport efficiency of the second negative electrode active material layer, and thus is beneficial to improving the kinetic performance of the lithium-ion secondary battery; the volume particle size distribution Dv502 of the second artificial graphite satisfies 10 μm ≤ Dv502 ≤ 15.5 μm. When Dv502 ≥ 10 μm, the volume particle size distribution Dv502 of the second artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the crushing process, and thus is beneficial to improving the storage performance of the second negative electrode active material layer; when Dv502 ≤ 18 μm, the risk of reduction in the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the second artificial graphite can be reduced, and the energy density of the first negative electrode active material layer can be improved; R2 of the second artificial graphite satisfies 0.12 ≤ R2 ≤ 0.25, the surface defect degree of the second artificial graphite is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer; by setting the first negative electrode active material layer and the second negative electrode active material layer on the negative electrode current collector, pore structures in different directions are formed, the ion transport path is increased, and it is further beneficial to improving the kinetic performance of the lithium-ion secondary battery. Therefore, the technical solution of the embodiment of the present application can enable the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance.

[0007] In a possible implementation manner, 15 μm ≤ Dv501 ≤ 16 μm; and / or, 11 μm ≤ Dv502 ≤ 13.5 μm.

[0008] In the above technical solution, the first artificial graphite and the second artificial graphite have a suitable volume particle size distribution, which can improve the storage performance and energy density of the negative electrode active material layer, and is beneficial for lithium-ion secondary batteries to have both high energy density, storage performance and kinetic performance.

[0009] In a possible implementation, the specific surface area S of the first artificial graphite satisfies: 0.8 m 2 / g≤S≤1.5m 2 / g.

[0010] In the above technical solution, the first artificial graphite has a suitable specific surface area, which is conducive to reducing the side reaction between the first artificial graphite and the electrolyte, improving the storage performance of the negative electrode active material layer, and making the lithium-ion secondary battery have high energy density, storage performance and kinetic performance. The specific surface area of ​​the first artificial graphite is ≥0.8m 2 / g, the larger the specific surface area of ​​the first artificial graphite, the smaller the particle size of the first artificial graphite, the higher the gram capacity and compaction density of the first artificial graphite, and thus the higher the energy density of the lithium-ion secondary battery; the specific surface area of ​​the first artificial graphite is ≤1.5m 2 / g, the specific surface area of ​​the first artificial graphite is small, which is beneficial to reducing the side reaction between the first artificial graphite and the electrolyte and improving the storage performance of the lithium ion secondary battery.

[0011] In a possible implementation, the disorder degree R2 of the second artificial graphite satisfies: R1 <R2≤0.25。

[0012] The R value can characterize the degree of surface defects of the material. The smaller the value, the lower the degree of surface defects of the material. By setting the R2 of the second artificial graphite to meet the above range, its surface defect degree can be adjusted to improve the ion transmission rate, which is beneficial for the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance. In the case where the R2 of the second artificial graphite is greater than R1, the surface defect degree of the second artificial graphite is higher than that of the first artificial graphite, which is beneficial for making the ion transmission efficiency of the second negative electrode active material layer higher and improving the kinetic performance of the negative electrode active material layer; in the case where the R2 of the second artificial graphite is less than or equal to 0.25, the surface defect degree of the second artificial graphite is too high, the active lithium consumption degree is increased, and the storage performance of the lithium-ion secondary battery is reduced.

[0013] In a possible implementation, the gram capacity of the first artificial graphite is greater than or equal to the gram capacity of the second artificial graphite.

[0014] In the above technical solution, by setting the gram capacity of the first artificial graphite to be greater than or equal to the gram capacity of the second artificial graphite, the difference in gram capacity between the first negative electrode active material layer and the second negative electrode active material layer can be increased. By setting the first artificial graphite on the side close to the negative electrode current collector, the first negative electrode active material layer can have a high gram capacity, which is beneficial to improve the energy density of the lithium-ion secondary battery.

[0015] In a possible implementation, the gram capacity of the first artificial graphite is 356 mAh / g to 363 mAh / g; the gram capacity of the second artificial graphite is 353 mAh / g to 358 mAh / g.

[0016] In the above technical solution, by setting the gram capacity of the first artificial graphite and the second artificial graphite to meet the above range, it is beneficial for the first negative electrode active material layer and the second negative electrode active material layer to have a high gram capacity, and it is also beneficial to achieve that the gram capacity of the first artificial graphite is greater than or equal to the gram capacity of the second artificial graphite, thereby facilitating the improvement of the energy density of the lithium-ion secondary battery.

[0017] In a possible implementation manner, the powder compaction density of the first artificial graphite under a pressure of 50 KN is greater than or equal to the powder compaction density of the second artificial graphite under a pressure of 50 KN.

[0018] In the above technical scheme, by setting the powder compaction density of the first artificial graphite to be greater than or equal to the powder compaction density of the second artificial graphite, the compression difference between the first negative electrode active material layer and the second negative electrode active material layer can be increased, so that ions can smoothly pass through the low-compression second negative electrode active material layer, thereby improving the kinetic performance of the lithium-ion secondary battery, which is beneficial for the lithium-ion secondary battery to have a combination of high energy density, storage performance and kinetic performance.

[0019] In a possible implementation, the powder compaction density of the first artificial graphite under a pressure of 50 KN is 1.75 g / cc to 1.94 g / cc; the powder compaction density of the second artificial graphite under a pressure of 50 KN is 1.70 g / cc to 1.90 g / cc.

[0020] In the above technical scheme, by setting the powder compaction density of the first artificial graphite and the powder compaction density of the second artificial graphite to meet the above range, it is beneficial for the first negative electrode active material layer and the second negative electrode active material layer to have a high compaction density, and it is also beneficial to achieve that the powder compaction density of the first artificial graphite is greater than or equal to the powder compaction density of the second artificial graphite, thereby improving the energy density and kinetic performance of the lithium-ion secondary battery, and is beneficial for the lithium-ion secondary battery to have a combination of high energy density, storage performance and kinetic performance.

[0021] In a possible implementation, the second artificial graphite further includes primary particles, and based on the total mass of the second artificial graphite, a mass ratio of the primary particles of the second artificial graphite to the secondary particles satisfies 30:70 to 10:90.

[0022] In the above technical solution, by setting the second artificial graphite to include primary particles, the mass ratio of the primary particles to the secondary particles of the second artificial graphite is within the range of 30:70 to 10:90, and the primary particles of the second artificial graphite can be filled on the surface of the secondary particles and in the gaps between the particles, reducing the phenomenon of accumulation between the particles due to excessive primary particles, which is beneficial to improving the energy density, storage performance and kinetic performance of the second negative electrode active material layer, thereby facilitating the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance. When the mass ratio of the primary particles to the secondary particles of the second artificial graphite is greater than or equal to 30:70, the primary particles can be filled on the surface of the secondary particles and in the gaps between the particles. On the one hand, the surface active points of the highly isotropic secondary particles can be reduced, and the probability of adsorbing other substances in the second negative electrode active material layer can be reduced, thereby reducing the degree of surface defects of the secondary particles, which is beneficial to improving the storage performance of the lithium-ion secondary battery; on the other hand, the primary particles have a low degree of surface defects, good surface integrity and uniformity, and are easy to disperse, which can reduce the amount of dispersant added during the preparation of the second negative electrode active material layer, and reduce the increase in the amount of dispersant added. This results in a decrease in the proportion of active materials in the second negative electrode active material layer, reducing the probability of a decrease in the energy density of the lithium-ion secondary battery; when the mass ratio of the primary particles to the secondary particles of the second artificial graphite is less than or equal to 10:90, the phenomenon of accumulation between particles due to excessive primary particles can be reduced, which is beneficial to shortening the ion transmission channel, increasing the ion transmission efficiency, and improving the kinetic performance of the lithium-ion secondary battery; the primary particles with a smaller particle size have a lower degree of surface defects, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer, thereby facilitating the lithium-ion secondary battery to have a balance between high energy density, storage performance and kinetic performance.

[0023] In a possible implementation, the OI value of the first artificial graphite is greater than the OI value of the second artificial graphite; and / or the OI value OI1 of the secondary particles satisfies: 2≤OI1≤5; and / or the OI value OI2 of the primary particles of the second artificial graphite satisfies: 7≤OI2≤10; and / or the OI value OI3 of the first artificial graphite satisfies: OI2≤OI3≤11.

[0024] In the above technical solution, the second artificial graphite with a lower OI value can provide more ion embedding points, which is beneficial to the diffusion of ions and improves the kinetic performance of the lithium-ion secondary battery; the first artificial graphite has a higher OI value, so that the OI value of the first negative electrode active material layer is higher, and the first negative electrode active material layer is arranged between the second negative electrode active material layer and the negative electrode current collector, which can increase the compaction density and gram capacity of the negative electrode sheet, thereby facilitating the improvement of the energy density and storage performance of the lithium-ion secondary battery, so that the lithium-ion secondary battery has both high energy density, storage performance and kinetic performance.

[0025] In a possible implementation, the second artificial graphite satisfies at least one of the following conditions: the volume particle size distribution Dv503 of the secondary particles of the second artificial graphite satisfies: 13μm≤Dv503≤18μm; the powder compaction density of the secondary particles of the second artificial graphite under a pressure of 50KN is 1.81g / cc~1.92g / cc; the gram capacity of the secondary particles of the second artificial graphite is 353.0mAh / g~358.2mAh / g. In this way, by setting the volume particle size distribution of the secondary particles of the second artificial graphite to meet the above range, the second negative electrode active material layer can have a suitable volume particle size distribution, and the combination of particles is more reasonable, which is conducive to improving the gram capacity and compaction density of the second artificial graphite; the second artificial graphite has a high powder compaction density and a high gram capacity, which is conducive to improving the energy density of the lithium-ion secondary battery, so that the lithium-ion secondary battery has both high energy density, storage performance and dynamic performance.

[0026] In a possible implementation, the second artificial graphite satisfies at least one of the following conditions: the volume particle size distribution Dv504 of the primary particles of the second artificial graphite satisfies: 7μm≤Dv504≤9μm; the volume particle size distribution Dv1 of the primary particles of the second artificial graphite satisfies: Dv1>3μm; the powder compaction density of the primary particles of the second artificial graphite under a pressure of 50KN is 1.78g / cc~1.80g / cc; the gram capacity of the primary particles of the second artificial graphite is 354.1mAh / g~358.6mAh / g.

[0027] In the above technical solution, the primary particles of the second artificial graphite have appropriate particle sizes, which can enable the second artificial graphite to have an appropriate particle size distribution, improve the tap density and specific capacity of the second negative electrode active material layer, and are beneficial to improving the energy density of the lithium-ion secondary battery; by setting Dv1>3μm, the volume proportion of fine powder particles (fine powder particles can refer to particles with a particle size less than or equal to 3μm) in the primary particles of the second artificial graphite is less than 1%. The primary particles have smaller particle sizes and can fill the surfaces and particle gaps of the secondary particles, thereby reducing the surface defect degree of the secondary particles, reducing the voids between particles, improving the ion transport efficiency of the negative electrode sheet, and improving the kinetic performance and storage performance of the lithium-ion secondary battery, which is beneficial to making the lithium-ion secondary battery take into account high energy density, storage performance and kinetic performance.

[0028] In a possible implementation manner, the negative electrode sheet satisfies at least one of the following conditions: the tap density of the negative electrode sheet under 50KN is 1.67g / cc to 1.75g / cc; the specific capacity of the negative electrode sheet is 357mAh / g to 360mAh / g; the areal density of the negative electrode sheet is 5.0mg / cm 2 ~25.0mg / cm 2 ; the thickness d of the negative electrode sheet satisfies: 70μm≤d≤250μm. In this way, the negative electrode sheet can have an appropriate thickness, a high areal density and a tap density, which is beneficial to making the lithium-ion secondary battery take into account high energy density, storage performance and kinetic performance.

[0029] In a second aspect, a method for preparing a lithium-ion secondary battery is provided, including: crushing and classifying calcined needle coke to obtain a first aggregate, and performing surface shaping treatment on the first aggregate to obtain primary particles; performing high-temperature graphitization treatment on the primary particles to obtain a first artificial graphite, the volume particle size distribution Dv501 of the first artificial graphite satisfies: 13μm≤Dv501≤18μm, and the R1 of the first artificial graphite satisfies: 0<R1≤0.14; where, R = I D1 / I G1 ,I D1 is the intensity of the maximum peak within the range of 1300cm -1 ~1400cm -1 in the Raman spectrum of the first artificial graphite, which is the intensity of the D peak, and I G1 is the intensity of the maximum peak within the range of 1535cm -1 ~1635cm -1The maximum peak intensity within the range is the intensity of the G peak; the needle coke is crushed and classified to obtain a second aggregate, and the second aggregate is subjected to surface shaping treatment and mixed with a binder for granulation to obtain an intermediate material including secondary particles; the intermediate material is subjected to high-temperature graphitization treatment to obtain a second artificial graphite, and the volume particle size distribution Dv502 of the second artificial graphite satisfies: 10 μm ≤ Dv502 ≤ 15.5 μm; the R2 of the second artificial graphite satisfies: R1 < R2 ≤ 0.25; where, R2 = I D2 / I G2 , I D2 is the maximum peak intensity within the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the second artificial graphite, which is the intensity of the D peak, and I G2 is the maximum peak intensity within the range of 1535 cm -1 -1635 cm -1 in the Raman spectrum of the second artificial graphite, which is the intensity of the G peak; the first artificial graphite is used to prepare a first negative electrode slurry, and the first negative electrode slurry is coated on at least one surface of a negative electrode current collector to prepare a first negative electrode active material layer; the second artificial graphite is used to prepare a second negative electrode slurry, and the second negative electrode slurry is coated on the surface of the first negative electrode active material layer to prepare a negative electrode plate provided with a second negative electrode active material layer; a positive electrode plate, the negative electrode plate, and a separator are provided and assembled into an electrode assembly, and the electrode assembly is placed in an outer package for encapsulation, and an electrolyte is injected and encapsulated to obtain a lithium ion secondary battery.

[0030] In the preparation method of the lithium ion secondary battery according to the embodiment of the present application, by crushing, classifying, and surface shaping the calcined needle coke, primary particles with appropriate particle sizes and a relatively low degree of surface defects are obtained, which is beneficial to obtaining a first artificial graphite with a volume particle size distribution Dv501 satisfying 13 μm ≤ Dv501 ≤ 18 μm; performing high-temperature graphitization treatment on the primary particles can further reduce the degree of surface defects, which is beneficial to making R1 of the first artificial graphite satisfy 0 < R1 ≤ 0.14; by respectively crushing, classifying, surface shaping, and mixing and granulating the needle coke, an intermediate material including secondary particles with appropriate particle sizes and a relatively low degree of surface defects is obtained, and the intermediate material is subjected to high-temperature graphitization treatment, which is beneficial to obtaining a second artificial graphite with a volume particle size distribution Dv502 satisfying 10 μm ≤ Dv502 ≤ 15.5 μm, and is beneficial to making R2 of the second artificial graphite satisfy 0.12 ≤ R2 ≤ 0.25; using the first artificial graphite and the second artificial graphite to prepare a negative electrode plate to prepare a lithium ion secondary battery is beneficial to the lithium ion secondary battery to take into account high energy density, storage performance, and high energy density.

[0031] In a possible implementation, the volatile matter of the calcined needle coke is ≤2%, and the sulfur content is ≤0.5%; and / or, the volatile matter of the needle green coke is ≤8%, and the sulfur content is ≤0.6%. In this way, by using calcined needle coke and needle green coke with relatively complete crystal structures, it is beneficial to obtain the first artificial graphite and the second artificial graphite with lower surface defect levels, reduce the consumption of active lithium, and improve the storage performance of lithium-ion secondary batteries; the volatile matter and sulfur content of the needle green coke are higher than those of the calcined needle coke, which can make the surface defect level of the second artificial graphite higher than that of the first artificial graphite, which is beneficial to improve the ion transfer efficiency in the second negative electrode active material layer, improve the kinetic performance of the negative electrode active material layer, and further help the lithium-ion secondary battery to have both high energy density, storage performance and kinetic performance.

[0032] In a possible implementation, the surface shaping treatment includes at least one of grinding, screening, spheroidization, and coating treatment. In this way, the surface defect degree of the first artificial graphite and the second artificial graphite can be reduced through the surface shaping treatment, which is beneficial to improving the storage performance of the negative electrode active material layer, and further beneficial to making the lithium-ion secondary battery have high energy density, storage performance and kinetic performance.

[0033] In a possible implementation, the processing temperature of the high-temperature graphitization is greater than or equal to 3000° C. In this way, the high-temperature graphitization is conducive to forming the first artificial graphite and the second artificial graphite with more complete crystal structures, thereby improving the powder compaction density of the first artificial graphite and the second artificial graphite and reducing the degree of surface defects, improving the energy density and storage performance of the lithium-ion secondary battery, and making it conducive to making the lithium-ion secondary battery have high energy density, storage performance and dynamic performance.

[0034] In a possible implementation, the intermediate material further includes primary particles obtained by performing surface shaping treatment on the second aggregate, and based on the total mass of the intermediate material, a mass ratio of the primary particles to the secondary particles satisfies 30:70 to 10:90.

[0035] In the above technical scheme, the secondary particles can be agglomerates of primary particles. The orientations of different primary particles in the secondary particles are not completely consistent, which is conducive to obtaining highly isotropic secondary particles and improving the kinetic properties of the second negative electrode active material layer. By setting the mass ratio of primary particles to secondary particles in the range of 30:70 to 10:90, the primary particles can be filled on the surface of the secondary particles and in the gaps between the particles, which is conducive to improving the energy density, storage performance and kinetic properties of the second negative electrode active material layer, thereby helping to make lithium-ion secondary batteries have both high energy density, storage performance and kinetic properties. When the mass ratio of primary particles to secondary particles is greater than or equal to 30:70, the primary particles can be filled on the surface of the secondary particles and in the gaps between the particles. On the one hand, the surface active points of the highly isotropic secondary particles can be reduced, and the probability of adsorbing other substances in the second negative electrode active material layer can be reduced, thereby reducing the degree of surface defects of the secondary particles, which is beneficial to improving the storage performance of the lithium-ion secondary battery; on the other hand, the primary particles have a low degree of surface defects, good surface integrity and uniformity, and are easy to disperse, which can reduce the increase in the amount of dispersant and suspending agent added during the preparation of the second negative electrode active material layer, resulting in a decrease in the proportion of active substances in the second negative electrode active material layer, and reducing the probability of a decrease in the energy density of the lithium-ion secondary battery; when the mass ratio of primary particles to secondary particles is less than or equal to 10:90, the phenomenon of accumulation between particles caused by excessive primary particles can be reduced, which is beneficial to shortening the ion transmission channel, increasing the ion transmission efficiency, and improving the kinetic performance of the lithium-ion secondary battery; the primary particles with smaller particle sizes have a lower degree of surface defects, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer, which is beneficial to the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance.

[0036] In a third aspect, an electrical device is provided, comprising a lithium-ion secondary battery according to the first aspect and any possible implementation thereof; and / or a lithium-ion secondary battery obtained by the preparation method according to the second aspect and any possible implementation thereof, wherein the lithium-ion secondary battery is used to provide electrical energy to the electrical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0038] Figure 1 A schematic diagram of a negative electrode sheet according to an embodiment of the present application;

[0039] Figure 2This is a SEM image of a negative electrode active material layer in a negative electrode sheet according to an embodiment of the present application;

[0040] Figure 3 A schematic diagram of a negative electrode active material layer in a negative electrode sheet according to an embodiment of the present application;

[0041] Figure 4 A schematic diagram of a lithium-ion battery cell according to an embodiment of the present application;

[0042] Figure 5 A schematic diagram of a method for preparing a lithium-ion secondary battery according to an embodiment of the present application;

[0043] Figure 6 A schematic diagram of a lithium-ion secondary battery according to an embodiment of the present application;

[0044] Figure 7 A schematic diagram of an electrical device according to an embodiment of the present application;

[0045] Figure 8 A schematic diagram of an electrical device according to an embodiment of the present application;

[0046] Figure numerals: 1: vehicle; 10: lithium-ion secondary battery; 30: controller; 40: motor; 11: casing; 111: first casing part; 112: second casing part; 3: lithium-ion battery cell; 31: casing; 32: end cover assembly; 33: electrode assembly; 34: current collecting member; 330: electrode assembly body; 331: pole ear; 322: electrode terminal; 5: negative electrode pole piece; 50: negative electrode current collector; 51: negative electrode active material layer; 511: first negative electrode active material layer; 512: second negative electrode active material layer. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.

[0048] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0049] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field of this application; the terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned drawings and any variations thereof are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship.

[0051] The "embedding" process in the embodiments of the present application refers to the process in which lithium ions are embedded in the positive electrode active material and the negative electrode active material due to an electrochemical reaction. The "extraction" and "de-embedding" processes described in the present application refer to the process in which lithium ions are extracted from the positive electrode active material and the negative electrode active material due to an electrochemical reaction.

[0052] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.

[0053] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", and "attached" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0054] The term "and / or" in this application is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Usually, a lithium-ion battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator. During the charge and discharge process of a lithium-ion battery cell, active ions are embedded and extracted back and forth between the positive electrode plate and the negative electrode plate. The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The separator is arranged between the positive electrode plate and the negative electrode plate, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through. During the charging process of a lithium-ion secondary battery, lithium ions are extracted from the positive electrode active material, move and embed into the negative electrode active material; and during the discharge process, lithium ions are extracted from the negative electrode active material, move and embed into the positive electrode active material.

[0055] The development of battery technology must consider multiple design factors at the same time, such as energy density, cycle life, capacity retention, charge and discharge rate, reliability, etc. The design of the negative electrode sheet is crucial to the performance of lithium-ion secondary batteries. Among them, the negative electrode active material in the negative electrode sheet directly affects the high energy density, storage performance and kinetic performance of lithium-ion secondary batteries.

[0056] Specifically, the use of graphite materials with high gram weight and high powder compaction density can improve the energy density of the negative electrode. High-gram-weight graphite materials can store more ions in the same volume, thereby improving the energy density of lithium-ion secondary batteries. However, the interlayer spacing of high-gram-weight graphite materials is relatively small, which may lead to lower charge and discharge rates, longer charging times, and decreased kinetic performance during the charge and discharge process.

[0057] The use of graphite materials with high powder compaction density is beneficial to reduce the risk of graphite being crushed during the preparation of negative electrode plates, increase the energy density of the negative electrode plates, and thus increase the energy density of lithium-ion secondary batteries. However, higher powder compaction density may lead to enhanced interactions between graphite layers and reduced structural stability, thereby reducing the storage performance of lithium-ion secondary batteries.

[0058] In view of this, an embodiment of the present application provides a lithium-ion secondary battery, including a negative electrode plate, the negative electrode plate includes a negative electrode active material layer, the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer is located between the negative electrode current collector and the second negative electrode active material layer, wherein, the first negative electrode active material layer includes a first artificial graphite, the first artificial graphite includes primary particles, and the volume particle size distribution Dv501 of the first artificial graphite satisfies: 13 μm ≤ Dv501 ≤ 18 μm; the R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14; wherein, R = I D1 / I G1 ,I D1 is the intensity of the D peak which is the maximum peak intensity in the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the first artificial graphite, and I G1 is the intensity of the G peak which is the maximum peak intensity in the range of 1535 cm -1 -1635 cm -1 in the Raman spectrum of the first artificial graphite; the second negative electrode active material layer includes a second artificial graphite; the second artificial graphite includes secondary particles, and the volume particle size distribution Dv502 of the second artificial graphite satisfies: 10 μm ≤ Dv502 ≤ 15.5 μm; the R2 of the second artificial graphite satisfies: 0.12 ≤ R2 ≤ 0.25; wherein, R2 = I D2 / I G2 ,I D2 is the intensity of the D peak which is the maximum peak intensity in the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the second artificial graphite, and I G2 is the intensity of the G peak which is the maximum peak intensity in the range of 1535 cm -1 -1635 cm -1 in the Raman spectrum of the second artificial graphite.

[0059] By setting the first negative electrode active material layer to include first artificial graphite, the first artificial graphite includes primary particles, and the surface defect degree of the primary particles is relatively low, which is beneficial to reducing the surface defect degree of the first artificial graphite; the volume particle size distribution Dv501 of the first artificial graphite satisfies 13 μm ≤ Dv501 ≤ 18 μm. When Dv501 ≥ 13 μm, the volume particle size distribution Dv501 of the first artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the material crushing process, thereby being beneficial to improving the storage performance of the first negative electrode active material layer; when Dv501 ≤ 18 μm, the risk of reduction in the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the first artificial graphite can be reduced, and the energy density of the first negative electrode active material layer can be improved; R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14, the first artificial graphite has good integrity and uniformity, and the surface defect degree is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the first negative electrode active material layer, thereby being beneficial to the lithium-ion secondary battery to take into account high energy density and storage performance; by setting the second negative electrode active material layer to include second artificial graphite, the second artificial graphite includes secondary particles, and the isotropy of the secondary particles is relatively high, which can improve the ion transport efficiency of the second negative electrode active material layer, thereby being beneficial to improving the kinetic performance of the lithium-ion secondary battery; the volume particle size distribution Dv502 of the second artificial graphite satisfies 10 μm ≤ Dv502 ≤ 15.5 μm. When Dv502 ≥ 10 μm, the volume particle size distribution Dv502 of the second artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the crushing process, thereby being beneficial to improving the storage performance of the second negative electrode active material layer; when Dv502 ≤ 15.5 μm, the risk of reduction in the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the second artificial graphite can be reduced, and the energy density of the second negative electrode active material layer can be improved; R2 of the second artificial graphite satisfies 0.12 ≤ R2 ≤ 0.25, the surface defect degree of the second artificial graphite is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer; by setting the first negative electrode active material layer and the second negative electrode active material layer on the negative electrode current collector, a pore structure in different directions is formed, and the ion transport path is increased, which is further beneficial to improving the kinetic performance of the lithium-ion secondary battery. Therefore, the technical solution of the embodiment of the present application can enable the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance.

[0060] [Negative electrode sheet]

[0061] Figure 1 It is a schematic diagram of the negative electrode sheet of an embodiment of the present application. For example, in combination with Figure 1As shown, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector, the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer, and the first negative electrode active material layer is located between the negative electrode current collector and the second negative electrode active material layer.

[0062] The negative electrode current collector 50 has two opposite sides along its own thickness direction, and the negative electrode active material layer 51 is arranged on any one or both of the two opposite surfaces of the negative electrode current collector 50, the first negative electrode active material layer 511 is arranged between the negative electrode current collector 50 and the second negative electrode active material layer 512, and the first negative electrode active material layer 511 is located on the side close to the negative electrode current collector 50.

[0063] As an example, the negative electrode active material layer 51 is disposed on one side surface of the negative electrode current collector 50 . As another example, the negative electrode active material layer 51 is disposed on both side surfaces of the negative electrode current collector 50 .

[0064] As an example, the negative electrode current collector can be a metal foil, a foamed metal or a composite current collector. For example, as the metal foil, aluminum or stainless steel treated with silver, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium, etc. can be used. The composite current collector may include a polymer material base and a metal layer. The foamed metal may be a nickel foam, a copper foam, an aluminum foam, an alloy foam, or carbon foam, etc. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0065] Figure 2 This is a SEM image of the negative electrode active material layer of an embodiment of the present application, combined with Figure 2 As shown, the first negative electrode active material layer includes a first artificial graphite, the first artificial graphite includes primary particles, the second negative electrode active material layer includes a second artificial graphite, the second artificial graphite includes secondary particles, and a secondary particle can be composed of two or more primary particles to form a larger particle as a whole. The secondary particles are relatively smooth on the outside, while the pores are still retained inside, which can increase the isotropy of the secondary particles and improve the ion transfer rate in the second negative electrode active material.

[0066] Combination Figure 3 As shown, Figure 3The figure shows a schematic diagram of the negative electrode active material layer in the negative electrode tab of an embodiment of the present application. The first negative electrode active material layer is disposed between the negative electrode current collector and the second negative electrode active material layer. Among them, the first negative electrode active material layer includes first artificial graphite, the first artificial graphite includes primary particles, and the volume particle size distribution Dv501 of the first artificial graphite satisfies: 13 μm ≤ Dv501 ≤ 18 μm; the R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14; where, R = I D1 / I G1 ,I D1 is the intensity of the maximum peak within the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the first artificial graphite, which is the intensity of the D peak, I G1 is the intensity of the maximum peak within the range of 1535 cm -1 -1635 cm -1 in the Raman spectrum of the first artificial graphite, which is the intensity of the G peak; the second negative electrode active material layer includes second artificial graphite; the second artificial graphite includes secondary particles, and the volume particle size distribution Dv502 of the second artificial graphite satisfies: 10 μm ≤ Dv502 ≤ 15.5 μm; the R2 of the second artificial graphite satisfies: 0.12 ≤ R2 ≤ 0.25; where, R2 = I D2 / I G2 ,I D2 is the intensity of the maximum peak within the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the second artificial graphite, which is the intensity of the D peak, I G2 is the intensity of the maximum peak within the range of 1535 cm -1 -1635 cm -1 in the Raman spectrum of the second artificial graphite, which is the intensity of the G peak.

[0067] Primary particles may refer to unagglomerated particles. The surface of the primary particles has good integrity and uniformity, and the degree of surface defects is relatively low.

[0068] Secondary particles may refer to particles formed by granulating primary particles of multiple second artificial graphites and then obtained through steps such as graphitization. Secondary particles may be aggregates of primary particles of the second artificial graphite. The orientations of different particles in the secondary particles are not completely consistent. There is still a certain pore structure inside the secondary particles, making the secondary particles have a relatively high isotropy, which can improve the ion transport efficiency of the second negative electrode active material layer and is beneficial to improving the kinetic performance of the lithium-ion secondary battery.

[0069] The R value can be obtained by the surface scanning mode of the laser micro-confocal Raman spectrometer. As an example, specifically, a laser micro-confocal Raman spectrometer (such as a high-precision Renishaw laser micro-confocal Raman spectrometer) is used, a laser wavelength of 532nm is selected, and an appropriate amount of sample is taken to perform a full-scale surface scan on its surface, the scanning area is 100μm×100μm, the step length is 2μm, and the total number of scanning points is 2500 points, thereby obtaining the R values ​​of different sites and the cumulative distribution curve of the R value of the surface scanning area.

[0070] The R value of the first artificial graphite and the second artificial graphite refers to the ratio of the peak heights of the D-band and the G-band of their Raman spectra, with the D-band position being 1300 cm -1 -1400cm -1 , the G peak position is 1535cm -1 -1635cm -1 The R value can characterize the degree of surface defects of the first artificial graphite and the second artificial graphite. The larger the R value is, the higher the degree of surface defects of the first artificial graphite and the second artificial graphite is.

[0071] The R value cumulative distribution curve refers to arranging the obtained 2500 R values ​​in ascending order, wherein the "1" in R1 is used to distinguish the R values ​​of other materials, for example, to distinguish it from R2 of the second artificial graphite.

[0072] Dv50 may refer to the particle size corresponding to when the cumulative particle size volume distribution number of a sample reaches 50%, or may refer to the particle size smaller than it accounting for 50%. The "1" in Dv501 is used to distinguish from the Dv50 of other materials, for example, to distinguish from Dv502 of the second artificial graphite, Dv503 of the secondary particles of the second artificial graphite, and Dv504 of the primary particles of the second artificial graphite.

[0073] Specifically, Dv501 can be 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, or any value within the above numerical range. Dv502 can be 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 15.5μm, or any value within the above numerical range. R1 can be 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, or any value within the above numerical range. R2 can be 0.12, 0.13, 0.14, 0.15, 0.16, 0.18, 0.2, 0.24, 0.25, or any value within the above numerical range.

[0074] In the embodiments of the present application, by setting the first negative electrode active material layer to include first artificial graphite, the first artificial graphite includes primary particles, and the surface defect degree of the primary particles is relatively low, which is beneficial to reducing the surface defect degree of the first artificial graphite; the volume particle size distribution Dv501 of the first artificial graphite satisfies 13 μm ≤ Dv501 ≤ 18 μm. When Dv501 ≥ 13 μm, the volume particle size distribution Dv501 of the first artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the material crushing process, thereby being beneficial to improving the storage performance of the first negative electrode active material layer; when Dv501 ≤ 18 μm, the risk of reduction in the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the first artificial graphite can be reduced, and the energy density of the first negative electrode active material layer can be improved; R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14, the first artificial graphite has good integrity and uniformity, and the surface defect degree is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the first negative electrode active material layer, thereby being beneficial to the lithium-ion secondary battery to take into account high energy density and storage performance; by setting the second negative electrode active material layer to include second artificial graphite, the second artificial graphite includes secondary particles, and the isotropy of the secondary particles is relatively high, which can improve the ion transport efficiency of the second negative electrode active material layer, thereby being beneficial to improving the kinetic performance of the lithium-ion secondary battery; the volume particle size distribution Dv502 of the second artificial graphite satisfies 10 μm ≤ Dv502 ≤ 15.5 μm. When Dv502 ≥ 10 μm, the volume particle size distribution Dv502 of the second artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the crushing process, thereby being beneficial to improving the storage performance of the second negative electrode active material layer; when Dv502 ≤ 15.5 μm, the risk of reduction in the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the second artificial graphite can be reduced, and the energy density of the second negative electrode active material layer can be improved; R2 of the second artificial graphite satisfies 0.12 ≤ R2 ≤ 0.25, the surface defect degree of the second artificial graphite is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer; by setting the first negative electrode active material layer and the second negative electrode active material layer on the negative electrode current collector, pore structures in different directions are formed, and the ion transport path is increased, which is further beneficial to improving the kinetic performance of the lithium-ion secondary battery. Therefore, the technical solution of the embodiments of the present application can enable the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance.

[0075] In some embodiments, 15 μm ≤ Dv501 ≤ 16 μm; and / or, 11 μm ≤ Dv502 ≤ 13.5 μm.

[0076] In the embodiment of the present application, the first artificial graphite and the second artificial graphite have a suitable volume particle size distribution, which can improve the storage performance and energy density of the negative electrode active material layer, and is beneficial for the lithium-ion secondary battery to have a combination of high energy density, storage performance and kinetic performance.

[0077] In some embodiments, the specific surface area S of the first artificial graphite satisfies: 0.8 m 2 / g≤S≤1.5m 2 / g.

[0078] The specific surface area may be a specific surface area obtained by a BET specific surface area adsorption method.

[0079] Specifically, S can be 0.8m 2 / g, 0.85m 2 / g, 0.9m 2 / g, 0.95m 2 / g, 1.0m 2 / g, 1.05m 2 / g, 1.1m 2 / g, 1.15m 2 / g, 1.2m 2 / g, 1.25m 2 / g, 1.3m 2 / g, 1.35m 2 / g, 1.4m 2 / g, 1.45m 2 / g, 1.5m 2 / g, or any value within the above numerical range.

[0080] In the embodiment of the present application, the first artificial graphite has a suitable specific surface area, which is conducive to reducing the side reaction between the first artificial graphite and the electrolyte, improving the storage performance of the negative electrode active material layer, and making the lithium-ion secondary battery have high energy density, storage performance and kinetic performance. The specific surface area of ​​the first artificial graphite is ≥ 0.8m 2 / g, the larger the specific surface area of ​​the first artificial graphite, the smaller the particle size of the first artificial graphite, the higher the gram capacity and compaction density of the first artificial graphite, and thus the higher the energy density of the lithium-ion secondary battery; the specific surface area of ​​the first artificial graphite is ≤1.5m 2 / g, the specific surface area of ​​the first artificial graphite is small, which is beneficial to reducing the side reaction between the first artificial graphite and the electrolyte and improving the storage performance of the lithium ion secondary battery.

[0081] In some embodiments, the disorder degree R2 of the second artificial graphite satisfies: R1 <R2≤0.25。

[0082] The R value can characterize the degree of surface defects of the material. The smaller the value, the lower the degree of surface defects of the material. By setting the R2 of the second artificial graphite to meet the above range, its surface defect degree can be adjusted to improve the ion transmission rate, which is beneficial for the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance. In the case where the R2 of the second artificial graphite is greater than R1, the surface defect degree of the second artificial graphite is higher than that of the first artificial graphite, which is beneficial for making the ion transmission efficiency of the second negative electrode active material layer higher and improving the kinetic performance of the negative electrode active material layer; in the case where the R2 of the second artificial graphite is less than or equal to 0.25, the surface defect degree of the second artificial graphite is too high, the active lithium consumption degree is increased, and the storage performance of the lithium-ion secondary battery is reduced.

[0083] In some embodiments, the gram capacity of the first artificial graphite is greater than or equal to the gram capacity of the second artificial graphite.

[0084] In the embodiment of the present application, by setting the gram capacity of the first artificial graphite to be greater than or equal to the gram capacity of the second artificial graphite, the difference in gram capacity between the first negative electrode active material layer and the second negative electrode active material layer can be increased. By setting the first artificial graphite close to the negative electrode current collector, the first negative electrode active material layer can have a high gram capacity, which is beneficial to improve the energy density of the lithium-ion secondary battery.

[0085] In some embodiments, the gram capacity of the first artificial graphite is 356 mAh / g to 363 mAh / g; the gram capacity of the second artificial graphite is 353 mAh / g to 358 mAh / g.

[0086] Specifically, the gram capacity of the first artificial graphite can be 356mAh / g, 357mAh / g, 358mAh / g, 359mAh / g, 360mAh / g, 361mAh / g, 362mAh / g, 363mAh / g, or any value within the above range. The gram capacity of the second artificial graphite can be 353mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 357mAh / g, 358mAh / g, or any value within the above range.

[0087] In the embodiment of the present application, by setting the gram capacity of the first artificial graphite and the second artificial graphite to meet the above-mentioned range, it is beneficial for the first negative electrode active material layer and the second negative electrode active material layer to have a high gram capacity, and it is also beneficial to achieve that the gram capacity of the first artificial graphite is greater than or equal to the gram capacity of the second artificial graphite, thereby facilitating the improvement of the energy density of the lithium-ion secondary battery.

[0088] In some embodiments, the powder compaction density of the first artificial graphite under a pressure of 50 KN is greater than or equal to the powder compaction density of the second artificial graphite under a pressure of 50 KN.

[0089] In the embodiment of the present application, by setting the powder compaction density of the first artificial graphite to be greater than or equal to the powder compaction density of the second artificial graphite, the compression difference between the first negative electrode active material layer and the second negative electrode active material layer can be increased, so that ions can smoothly pass through the low-compression second negative electrode active material layer, thereby improving the kinetic performance of the lithium-ion secondary battery, which is beneficial for the lithium-ion secondary battery to have a combination of high energy density, storage performance and kinetic performance.

[0090] In some embodiments, the powder compaction density of the first artificial graphite under a pressure of 50 KN is 1.75 g / cc to 1.94 g / cc; the powder compaction density of the second artificial graphite under a pressure of 50 KN is 1.70 g / cc to 1.90 g / cc.

[0091] Specifically, the powder compaction density of the first artificial graphite at 50KN can be 1.75g / cc, 1.80g / cc, 1.85g / cc, 1.90g / cc, 1.94g / cc, or any value within the above range. The powder compaction density of the second artificial graphite at 50KN can be 1.70g / cc, 1.75g / cc, 1.80g / cc, 1.85g / cc, 1.90g / cc, or any value within the above range.

[0092] In the embodiment of the present application, by setting the powder compaction density of the first artificial graphite and the powder compaction density of the second artificial graphite to meet the above-mentioned range, it is beneficial for the first negative electrode active material layer and the second negative electrode active material layer to have a high compaction density, and it is also beneficial to achieve that the powder compaction density of the first artificial graphite is greater than or equal to the powder compaction density of the second artificial graphite, thereby improving the energy density and kinetic performance of the lithium-ion secondary battery, and is beneficial for the lithium-ion secondary battery to have a combination of high energy density, storage performance and kinetic performance.

[0093] In some embodiments, the second artificial graphite further includes primary particles, and a mass ratio of the primary particles to the secondary particles of the second artificial graphite satisfies 30:70 to 10:90.

[0094] In the embodiment of the present application, by setting the second artificial graphite to include primary particles, the mass ratio of the primary particles to the secondary particles of the second artificial graphite is in the range of 30:70 to 10:90, and the primary particles of the second artificial graphite can be filled on the surface of the secondary particles and in the gaps between the particles, reducing the phenomenon of accumulation between the particles due to excessive primary particles, which is beneficial to improving the energy density, storage performance and kinetic performance of the second negative electrode active material layer, thereby facilitating the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance. When the mass ratio of the primary particles to the secondary particles of the second artificial graphite is greater than or equal to 30:70, the primary particles can be filled on the surface of the secondary particles and in the gaps between the particles. On the one hand, the surface active points of the highly isotropic secondary particles can be reduced, and the probability of adsorbing other substances in the second negative electrode active material layer can be reduced, thereby reducing the degree of surface defects of the secondary particles, which is beneficial to improving the storage performance of the lithium-ion secondary battery; on the other hand, the surface defect degree of the primary particles is low, the surface integrity and uniformity are good, and it is easy to disperse, which can reduce the amount of dispersant added in the preparation process of the second negative electrode active material layer, and reduce the increase in the amount of dispersant added. , resulting in a decrease in the proportion of active materials in the second negative electrode active material layer, and a probability of a decrease in the energy density of the lithium-ion secondary battery; when the mass ratio of the primary particles to the secondary particles of the second artificial graphite is less than or equal to 10:90, the phenomenon of accumulation between particles caused by excessive primary particles can be reduced, which is beneficial to shortening the ion transmission channel, increasing the ion transmission efficiency, and improving the kinetic performance of the lithium-ion secondary battery; the primary particles with smaller particle sizes have a lower degree of surface defects, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer, thereby helping the lithium-ion secondary battery to have a combination of high energy density, storage performance and kinetic performance.

[0095] In some embodiments, the OI value of the first artificial graphite is greater than the OI value of the second artificial graphite; and / or the OI value OI1 of the secondary particles satisfies: 2≤OI1≤5; and / or the OI value OI2 of the primary particles of the second artificial graphite satisfies: 7≤OI2≤10; and / or the OI value OI3 of the first artificial graphite satisfies: OI2≤OI3≤11.

[0096] In the embodiment of the present application, the OI values ​​of the first artificial graphite and the second artificial graphite can be tested by methods known in the art. For example, the XRD spectra of the first artificial graphite and the second artificial graphite are tested, and the OI values ​​are calculated by C004 / C110.

[0097] The second artificial graphite with a lower OI value can provide more ion embedding points, which is beneficial to the diffusion of ions and improves the kinetic performance of the lithium-ion secondary battery; the first artificial graphite has a higher OI value, so that the OI value of the first negative electrode active material layer is higher. The first negative electrode active material layer is arranged between the second negative electrode active material layer and the negative electrode current collector, which can increase the compaction density and gram capacity of the negative electrode sheet, thereby facilitating the improvement of the energy density and storage performance of the lithium-ion secondary battery, so that the lithium-ion secondary battery has both high energy density, storage performance and kinetic performance.

[0098] In some embodiments, the second artificial graphite satisfies at least one of the following conditions: the volume particle size distribution Dv503 of the secondary particles of the second artificial graphite satisfies: 13μm≤Dv503≤18μm; the powder compaction density of the secondary particles of the second artificial graphite under a pressure of 50KN is 1.81g / cc~1.92g / cc; the gram capacity of the secondary particles of the second artificial graphite is 353.0mAh / g~358.2mAh / g.

[0099] Specifically, the powder compaction density of the secondary particles of the second artificial graphite at 50KN can be 1.81g / cc, 1.82g / cc, 1.83g / cc, 1.84g / cc, 1.85g / cc, 1.86g / cc, 1.87g / cc, 1.88g / cc, 1.89g / cc, 1.90g / cc, 1.91g / cc, 1.92g / cc, or any value within the above range. The gram capacity of the secondary particles of the second artificial graphite can be 353.0mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 357mAh / g, 358mAh / g, 358.2mAh / g, or any value within the above range.

[0100] By setting the volume particle size distribution of the secondary particles of the second artificial graphite to meet the above range, the second negative electrode active material layer can have a suitable volume particle size distribution, and the particles are more reasonably matched, which is beneficial to improving the gram capacity and compaction density of the second artificial graphite; the second artificial graphite has a high powder compaction density and a high gram capacity, which is beneficial to improving the energy density of the lithium-ion secondary battery, so that the lithium-ion secondary battery has high energy density, storage performance and kinetic performance.

[0101] In some embodiments, the particle size distribution of the second artificial graphite satisfies: 1≤(Dv90-Dv10) / Dv502≤1.6.

[0102] In some embodiments, the volume proportion φ of particles with a particle size of 6.5 μm to 22.5 μm in the second artificial graphite satisfies:

[0103] Dv10 represents the particle size corresponding to 10% of the cumulative particle size distribution percentage in a sample; Dv50 represents the particle size corresponding to 50% of the cumulative particle size distribution percentage in a sample; and Dv90 represents the particle size corresponding to 90% of the cumulative particle size distribution percentage in a sample.

[0104] In the embodiment of the present application, by setting the volume particle size distribution Dv10, Dv502, and Dv90 of the second artificial graphite to meet the above-mentioned range, it is beneficial for the second negative electrode active material layer to have a suitable volume particle size distribution, which is beneficial to improving the gram capacity and compaction density of the negative electrode sheet; the second artificial graphite has a high powder compaction density and high gram capacity, which is beneficial to improving the energy density of the negative electrode sheet.

[0105] In some embodiments, the second artificial graphite satisfies at least one of the following conditions: the volume particle size distribution Dv504 of the primary particles of the second artificial graphite satisfies: 7μm≤Dv504≤9μm; the volume particle size distribution Dv1 of the primary particles of the second artificial graphite satisfies: Dv1>3μm; the powder compaction density of the primary particles of the second artificial graphite under a pressure of 50KN is 1.78g / cc~1.80g / cc; the gram capacity of the primary particles of the second artificial graphite is 354.1mAh / g~358.6mAh / g.

[0106] Dv1 represents the particle size corresponding to the cumulative particle size distribution percentage in a sample reaching 1%.

[0107] Specifically, the volume particle size distribution Dv504 of the primary particles of the second artificial graphite can be 7μm, 8μm, 9μm, or any value within the above range. Dv1 can be 4μm, 5μm, 6μm, or any value within the above range. The powder compaction density of the primary particles of the second artificial graphite at 50KN can be 1.78g / cc, 1.79g / cc, 1.80g / cc, or any value within the above range. The gram capacity of the primary particles of the second artificial graphite can be 354.1mAh / g, 355mAh / g, 356mAh / g, 357mAh / g, 358mAh / g, 358.6mAh / g, or any value within the above range.

[0108] In the embodiment of the present application, the primary particles of the second artificial graphite have a suitable particle size, so that the second artificial graphite can have a suitable particle size distribution, which can increase the compaction density and gram capacity of the second negative electrode active material layer, and is beneficial to improving the energy density of the lithium-ion secondary battery; by setting Dv1>3μm, the volume proportion of fine powder particles (fine powder particles can refer to particles with a particle size less than or equal to 3μm) in the primary particles of the second artificial graphite is less than 1%, and the primary particles have a smaller particle size. The primary particles can be filled on the surface of the secondary particles and in the particle gaps, thereby reducing the degree of surface defects of the secondary particles, reducing the gaps between particles, improving the ion transfer efficiency of the negative electrode plate, and improving the kinetic performance and storage performance of the lithium-ion secondary battery, which is beneficial to make the lithium-ion secondary battery have both high energy density, storage performance and kinetic performance.

[0109] In some embodiments, in the second artificial graphite, (250±5) μm 2 The number of primary particles with a particle size greater than or equal to 30 μm is ≤ 10. In this way, the primary particles of the second artificial graphite have a smaller particle size, which is conducive to filling the surface of the secondary particles and the particle gaps.

[0110] In some embodiments, the negative electrode sheet satisfies at least one of the following conditions: the compaction density of the negative electrode sheet at 50KN is 1.67 / cm 3 ~1.75g / cc; the gram capacity of the negative electrode is 357mAh / g~360mAh / g; the surface density of the negative electrode is 5.0mg / cm 2 ~25.0mg / cm 2 , optionally, 5.5 mg / cm 2 ~22.5mg / cm 2 ; The thickness d of the negative electrode plate is 70μm≤d≤250μm, optionally, 90μm≤d≤220μm.

[0111] Specifically, the compaction density of the negative electrode sheet can be 1.67g / cc, 1.68g / cc, 1.69g / cc, 1.70g / cc, 1.71g / cc, 1.72g / cc, 1.73g / cc, 1.74g / cc, 1.75g / cc, or any value within the above range; the gram capacity of the negative electrode sheet can be 357mAh / g, 358mAh / g, 359mAh / g, 360mAh / g, or any value within the above range; the surface density of the negative electrode sheet can be 5.0mg / cm 2 、10.0mg / cm 2 、15.0mg / cm 2 、20.0mg / cm 2 , 25.0mg / cm 2, or any value within the above range; the thickness of the negative electrode plate can be 90μm, 120μm, 140μm, 160μm, 180μm, 200μm, 220μm, or any value within the above range.

[0112] In the embodiment of the present application, the negative electrode plate can have a suitable thickness, a high surface density and a compaction density, which is beneficial for the lithium-ion secondary battery to have a high energy density, storage performance and dynamic performance.

[0113] In some embodiments, based on the total mass of the negative electrode active material layer, the mass ratio of the first artificial graphite to the second artificial graphite satisfies: 30:70 to 50:50.

[0114] In the embodiment of the present application, by setting the mass ratio of the first artificial graphite to the second artificial graphite in the range of 30:70 to 50:50, it is beneficial to select a suitable mass ratio range according to actual use requirements, so that the lithium-ion secondary battery takes into account high energy density, storage performance and dynamic performance. When the mass ratio of the first artificial graphite to the second artificial graphite is greater than or equal to 30:70, the situation where the mass of the first artificial graphite is too low and the storage performance and energy density of the lithium-ion secondary battery decrease can be reduced; when the mass ratio of the first artificial graphite to the second artificial graphite is less than or equal to 50:50, the situation where the mass of the second artificial graphite is too low and the dynamic performance and energy density of the lithium-ion secondary battery decrease can be reduced.

[0115] In some embodiments, the negative electrode active material layer may further include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0116] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0117] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the first artificial graphite, the conductive agent, the binder and any other components are dispersed in a solvent (such as NMP) to form a first negative electrode slurry; the second artificial graphite, the conductive agent, the binder and any other components are dispersed in a solvent (such as NMP) to form a second negative electrode slurry; the first negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, a first negative electrode active material layer is formed on the negative electrode current collector, and then the second negative electrode slurry is coated on the first negative electrode active material layer, and the negative electrode sheet can be obtained after drying. It should be understood that the cold pressing process can also be set after the second negative electrode slurry is coated and dried.

[0118] [Positive electrode]

[0119] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector.

[0120] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0121] As an example, the positive electrode current collector may be a metal foil, a foam metal or a composite current collector. For example, as a metal foil, aluminum or stainless steel, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium with a silver surface treatment may be used. The foam metal may be a nickel foam, a copper foam, an aluminum foam, an alloy foam, or carbon foam. The composite current collector may include a polymer material base and a metal layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0122] In some embodiments, the positive electrode active material layer includes a positive electrode active material. Optionally, the positive electrode active material may include a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3Co1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0123] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0124] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0125] [Electrolytes]

[0126] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, semi-solid or fully solid.

[0127] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0128] For lithium-ion battery cells or lithium metal battery cells, the electrolyte salt may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0129] For lithium-ion battery cells or lithium metal battery cells, the solvent may include one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0130] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0131] The present application has no specific restrictions on the type of electrolyte, which can be selected according to the needs. The electrolyte can be liquid, semi-solid or solid.

[0132] [Isolation film]

[0133] The isolation membrane is a diaphragm. The present application has no particular limitation on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.

[0134] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0135] The positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process.

[0136] [Lithium-ion battery cells]

[0137] Figure 4 Schematic diagram of a lithium-ion battery cell according to an embodiment of the present application. Figure 4 As shown, the lithium-ion battery cell 3 is a square battery cell and includes a housing 31 , an end cover assembly 32 and an electrode assembly 33 disposed in the housing 31 .

[0138] The electrode assembly 33 may be made of a positive electrode sheet, a negative electrode sheet and a separator through a winding process or a lamination process.

[0139] The end cap assembly 32 includes an electrode terminal 322, such as Figure 4 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.

[0140] In some embodiments, the lithium-ion battery cell 3 includes an electrode assembly 33 , and the electrode assembly 33 includes an electrode assembly body 330 and a tab 331 extending from the electrode assembly body 330 .

[0141] The lithium-ion battery cell 3 further includes a current collecting member 34, which is used to connect the pole tab 331 of the electrode assembly 33 and the electrode terminal 322. For example, when the pole piece of the embodiment of the present application is a positive pole piece, one current collecting member 34 is used to connect the positive pole tab and the positive electrode terminal, and the other current collecting member 34 is used to connect the negative pole tab and the negative electrode terminal.

[0142] In the embodiment of the present application, the lithium-ion battery cell may be a secondary battery. A secondary battery refers to a battery cell that can be continuously used by activating active materials by charging after the battery cell is discharged.

[0143] In some embodiments, lithium-ion battery cells can be assembled into a battery module. The number of lithium-ion battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0144] In some embodiments, a lithium-ion battery cell may include a housing. The housing is used to encapsulate components such as an electrode assembly and an electrolyte. The housing may be a steel housing, an aluminum housing, a plastic housing (such as polypropylene), a composite metal housing (such as a copper-aluminum composite housing), or an aluminum-plastic film. The housing includes a shell and an end cap.

[0145] The lithium-ion battery mentioned in the embodiments of the present application may include one or more lithium-ion battery cells to provide a single physical module with higher voltage and capacity. When there are multiple lithium-ion battery cells, the multiple lithium-ion battery cells are connected in series, in parallel or in hybrid connection through a busbar component.

[0146] [Method for producing lithium-ion secondary battery]

[0147] Figure 5 FIG. 1 is a schematic diagram of a method for preparing a lithium-ion secondary battery according to an embodiment of the present application. Figure 5 As shown, the method 200 for preparing a lithium-ion secondary battery includes the following steps.

[0148] Step 210: Crush and classify the calcined needle coke to obtain the first aggregate, and perform surface shaping treatment on the first aggregate to obtain primary particles.

[0149] Step 220: Perform high-temperature graphitization treatment on the primary particles to obtain the first artificial graphite.

[0150] Step 230: Crush and classify the green needle coke to obtain the second aggregate, perform surface shaping treatment on the second aggregate, and mix it with a binder to granulate, obtaining an intermediate material including secondary particles.

[0151] Step 240: Perform high-temperature graphitization treatment on the intermediate material to obtain the second artificial graphite.

[0152] Step 250: Prepare the first negative electrode slurry using the first artificial graphite, and coat the first negative electrode slurry on at least one surface of the negative electrode current collector to prepare the first negative electrode active material layer.

[0153] Step 260: Prepare the second negative electrode slurry using the second artificial graphite, and coat the second negative electrode slurry on the surface of the first negative electrode active material layer to prepare a negative electrode plate provided with a second negative electrode active material layer.

[0154] Step 270: Provide a positive electrode plate, the negative electrode plate, and a separator membrane to assemble an electrode assembly, place the electrode assembly in an outer package for encapsulation, and inject an electrolyte and then encapsulate to obtain a lithium-ion secondary battery.

[0155] In the method for preparing a lithium-ion secondary battery according to the embodiment of the present application, by crushing, classifying, and performing surface shaping treatment on the calcined needle coke, primary particles with appropriate particle size and relatively low surface defect degree are obtained, which is beneficial to obtaining the first artificial graphite with a volume particle size distribution Dv501 satisfying 13 μm ≤ Dv501 ≤ 18 μm; performing high-temperature graphitization treatment on the primary particles can further reduce the surface defect degree, which is beneficial to making the R1 of the first artificial graphite satisfy 0 < R1 ≤ 0.14; by respectively crushing, classifying, performing surface shaping treatment, and mixing and granulating the green needle coke, an intermediate material including secondary particles with appropriate particle size and relatively low surface defect degree is obtained, and performing high-temperature graphitization treatment on the intermediate material is beneficial to obtaining the second artificial graphite with a volume particle size distribution Dv502 satisfying 10 μm ≤ Dv502 ≤ 15.5 μm, and is also beneficial to making the R2 of the second artificial graphite satisfy 0.12 ≤ R2 ≤ 0.25; using the first artificial graphite and the second artificial graphite to prepare the negative electrode plate to prepare a lithium-ion secondary battery is beneficial for the lithium-ion secondary battery to take into account high energy density, storage performance, and high energy density.

[0156] During the process of preparing the lithium-ion secondary battery, a binder, a conductive agent, and a solvent can also be respectively added and mixed to obtain the first negative electrode slurry and the second negative electrode slurry.

[0157] In some embodiments, the binder includes at least one of asphalt, phenolic resin, furfural resin, and epoxy resin.

[0158] In some embodiments, the mass ratio of the primary particles obtained by the second aggregate to the binder is 100:(3:5), and the primary particles and the binder are mixed according to the above mass ratio.

[0159] In some embodiments, the primary particles obtained from the first aggregate are uniformly mixed with asphalt in a mass ratio of 100:(0.5:2) and subjected to high-temperature graphitization treatment, which is beneficial for obtaining a first artificial graphite including a soft carbon coating layer.

[0160] In some embodiments, the volatile matter of the calcined needle coke is ≤2%, and the sulfur content is ≤0.5%; and / or, the volatile matter of the green needle coke is ≤8%, and the sulfur content is ≤0.6%.

[0161] In the embodiments of the present application, "needle coke" may be an intermediate product prepared by a delayed coking process of petroleum residue oil or coal tar pitch, which has not yet been subjected to a high-temperature calcination treatment.

[0162] "Calcined needle coke" may be a material obtained by using needle green coke as raw material and undergoing high-temperature calcination treatment (1200°C to 1500°C).

[0163] The volatile matter of a material refers to the mass lost when the material is heated under certain conditions, such as high temperature, oxygen-free environment, etc. The lower the volatile matter value of a material, the less volatile components in the material, such as water, low molecular weight organic matter, weak chemical bond parts, etc., the less surface impurities, and the fewer surface defects (such as surface holes, cracks, unsaturated bonds, etc.).

[0164] The sulfur content of a material refers to the mass content of sulfur in the material. The lower the sulfur content of a material, the lower the impurity content in the material.

[0165] Specifically, the volatile matter of the calcined needle coke can be 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, or any value within the above range. The sulfur content of the calcined needle coke can be 0.1wt.%, 0.2wt.%, 0.3wt.%, 0.4wt.%, 0.5wt.%, or any value within the above range. The volatile matter of the needle green coke can be 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, or any value within the above range. The sulfur content of the needle green coke can be 0.1wt.%, 0.2wt.%, 0.3wt.%, 0.4wt.%, 0.5wt.%, 0.6wt.%, or any value within the above range.

[0166] In the embodiment of the present application, by using calcined needle coke and needle green coke with relatively complete crystal structures, it is beneficial to obtain the first artificial graphite and the second artificial graphite with lower surface defect levels, reduce the consumption of active lithium, and improve the storage performance of the lithium-ion secondary battery; the volatile matter and sulfur content of the needle green coke are higher than those of the calcined needle coke, so that the surface defect level of the second artificial graphite can be higher than that of the first artificial graphite, which is beneficial to improve the ion transfer efficiency in the second negative electrode active material layer, improve the kinetic performance of the negative electrode active material layer, and further help the lithium-ion secondary battery to have both high energy density, storage performance and kinetic performance.

[0167] In some embodiments, the surface shaping treatment includes at least one of grinding, screening, spheroidization, and coating treatment. In this way, the surface defect degree of the first artificial graphite and the second artificial graphite can be reduced through the surface shaping treatment, which is beneficial to improving the storage performance of the negative electrode active material layer, and further beneficial to making the lithium ion secondary battery have high energy density, storage performance and kinetic performance.

[0168] In some embodiments, the coating treatment includes at least one of soft carbon coating, hard carbon coating, graphene coating, natural graphite coating, and carbon nanotube coating. The above coating treatment is beneficial to reducing the degree of surface defects of the first artificial graphite and the second artificial graphite, reducing the consumption of active lithium, and improving the storage performance of lithium-ion secondary batteries.

[0169] It should be understood that the test method for the coating layer is not limited in the embodiments of the present application, and the test methods known in the art can be used. As an example, a thin slice with a thickness of about 100 nm can be cut from the middle of the negative electrode active material particles by a focused ion beam (FIB), and then the thin slice is subjected to a TEM test, and it can be observed that the surface area includes the coating layer. The lattice fringes in the coating layer are partially ordered, and the electron diffraction pattern appears diffuse ring-shaped or partially halo-shaped, indicating that the coating layer includes soft carbon. The negative electrode active material is observed by transmission electron microscopy, and based on the difference in lattice fringes, the coating layer coated on the surface of the first artificial graphite or the second artificial graphite can be clearly observed.

[0170] In some embodiments, the temperature of the high-temperature graphitization treatment is greater than or equal to 3000° C. In this way, the high-temperature graphitization is conducive to forming the first artificial graphite and the second artificial graphite with more complete crystal structures, thereby increasing the powder compaction density of the first artificial graphite and the second artificial graphite and reducing the degree of surface defects, improving the energy density and storage performance of the lithium-ion secondary battery, and facilitating the lithium-ion secondary battery to have both high energy density, storage performance and dynamic performance.

[0171] It should be understood that the embodiment of the present application has no particular limitation on the temperature of the above-mentioned high-temperature graphitization treatment, as long as the purpose of the embodiment of the present application can be achieved. For example, the temperature of the high-temperature graphitization treatment is 3000°C to 3200°C.

[0172] In some embodiments, the intermediate material further includes primary particles obtained by surface shaping the second aggregate, and based on the total mass of the intermediate material, the mass ratio of the primary particles to the secondary particles satisfies 30:70 to 10:90.

[0173] In the embodiment of the present application, the secondary particles can be agglomerates of primary particles. The orientations of different primary particles in the secondary particles are not completely consistent, which is conducive to obtaining highly isotropic secondary particles and improving the kinetic properties of the second negative electrode active material layer. By setting the mass ratio of primary particles to secondary particles in the range of 30:70 to 90:10, the primary particles can be filled on the surface of the secondary particles and in the gaps between the particles, which is conducive to improving the energy density, storage performance and kinetic properties of the second negative electrode active material layer, thereby helping to make the lithium-ion secondary battery have both high energy density, storage performance and kinetic properties. When the mass ratio of primary particles to secondary particles is greater than or equal to 30:70, the primary particles can be filled on the surface of the secondary particles and in the gaps between the particles. On the one hand, the surface active points of the highly isotropic secondary particles can be reduced, and the probability of adsorbing other substances in the second negative electrode active material layer can be reduced, thereby reducing the degree of surface defects of the secondary particles, which is beneficial to improving the storage performance of the lithium-ion secondary battery; on the other hand, the primary particles have a low degree of surface defects, good surface integrity and uniformity, and are easy to disperse, which can reduce the increase in the amount of dispersant and suspending agent added during the preparation of the second negative electrode active material layer, resulting in a decrease in the proportion of active substances in the second negative electrode active material layer and the probability of a decrease in the energy density of the lithium-ion secondary battery; when the mass ratio of primary particles to secondary particles is less than or equal to 10:90, the phenomenon of accumulation between particles caused by excessive primary particles can be reduced, which is beneficial to shortening the ion transmission channel, increasing the ion transmission efficiency, and improving the kinetic performance of the lithium-ion secondary battery; the primary particles with smaller particle sizes have a lower degree of surface defects, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer, which is beneficial to the lithium-ion secondary battery to take into account high energy density, storage performance and kinetic performance.

[0174] In some embodiments, the primary particles and secondary particles of the second artificial graphite are mixed in the above-mentioned mass ratio to obtain mixed particles, and the mixed particles are evenly mixed with asphalt in a mass ratio of 100:(0.5:2), and subjected to high-temperature graphitization treatment, which is beneficial to obtaining a second artificial graphite including a soft carbon coating layer.

[0175] The present application embodiment does not limit the test method for the coating content, and a test method known in the art can be used. As an example, the total content of the coating can be tested by using a high-frequency infrared carbon-sulfur analyzer (C content analyzer, model HCS-140, Shanghai Dekai Instrument Co., Ltd.) according to GBT20123-2006 "Determination of total carbon and sulfur content of steel using infrared absorption method after combustion in a high-frequency induction furnace (conventional method)" to test the total content of the coating in the first artificial graphite and the second artificial graphite.

[0176] [Lithium-ion secondary battery]

[0177] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0178] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.

[0179] In some embodiments, lithium-ion secondary batteries can be assembled into a battery module. The number of batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0180] In some embodiments, the lithium-ion secondary battery may be located in an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0181] Figure 6 FIG. 1 is a schematic diagram of a lithium-ion secondary battery according to an embodiment of the present application. Figure 6 As shown, the lithium-ion secondary battery 10 may include a plurality of lithium-ion battery cells 3 to meet different power usage requirements.

[0182] The lithium-ion secondary battery 10 may further include a casing 11, the interior of the casing 11 being a hollow structure, and a plurality of lithium-ion battery cells 3 being contained in the casing 11. For example, a plurality of lithium-ion battery cells 3 are connected in parallel, in series, or in a mixed combination and placed in the casing 11. The casing 11 may include a first casing portion 111 and a second casing portion 112, which cover each other to form the casing 11. The shapes of the first casing portion 111 and the second casing portion 112 may be determined according to the shapes of the components contained therein, for example, may be determined according to the shape of the combination of the plurality of lithium-ion battery cells 3 contained therein, and at least one of the first casing portion 111 and the second casing portion 112 may have an opening. For example, as Figure 4As shown, the first box body 111 and the second box body 112 can both be hollow cuboids and each have an open face, the opening of the first box body 111 and the opening of the second box body 112 are arranged opposite to each other, and the first box body 111 and the second box body 112 are buckled together to form a box body 11 with a closed chamber, which can be used to accommodate multiple lithium-ion battery cells 3. Multiple lithium-ion battery cells 3 are connected in parallel, in series, or in a mixed combination and placed in the box body 11 formed by the buckling of the first box body 111 and the second box body 112.

[0183] For example, unlike Figure 6 As shown, only one of the first box body 111 and the second box body 112 may be a hollow cuboid with an opening, while the other is in a plate shape to cover the opening. Taking the second box body 112 as a hollow cuboid with an opening and the first box body 111 as a plate, the first box body 111 covers the opening of the second box body 112 to form a box body 11 with a closed chamber, which can be used to accommodate multiple lithium-ion battery cells 3.

[0184] In some embodiments, the lithium-ion secondary battery 10 may further include other components. For example, the lithium-ion secondary battery 10 may further include a busbar component, which may be used to achieve electrical connection between multiple lithium-ion battery cells 3, such as parallel connection, series connection, or mixed connection. Specifically, the busbar component may achieve electrical connection between the lithium-ion battery cells 3 by connecting the electrode terminals of the lithium-ion battery cells 3; or, the busbar component may also achieve electrical connection between the lithium-ion battery cells 3 by connecting other components of the lithium-ion battery cells 3. The busbar component may be fixed to the corresponding component of the lithium-ion battery cell 3 by welding, for example, it may be fixed to the electrode terminal, the sealing structure, or the housing by welding, etc., and the embodiments of the present application are not limited thereto.

[0185] The lithium-ion battery cells 3 can directly form the lithium-ion secondary battery 10 , or can first form a battery module, and then multiple battery modules form the lithium-ion secondary battery 10 .

[0186] In some embodiments, the lithium-ion secondary batteries can also be assembled into battery modules / battery packs. The number of battery modules contained in the lithium-ion secondary battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0187] [Electrical devices]

[0188] The embodiments of the present application provide an electrical device including at least one of the lithium-ion secondary battery, battery module, or battery pack provided in the present application. The lithium-ion secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0189] As an electrical device, a lithium-ion secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0190] Electrical equipment may be vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, electric tools, and the like. Vehicles may be fuel vehicles, gas vehicles, or new energy vehicles, and new energy vehicles may be pure electric vehicles, hybrid vehicles, or extended-range vehicles, and the like; spacecraft include airplanes, rockets, space shuttles, and spacecraft, and the like; electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like; electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools, and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, and the like. The embodiments of the present application do not impose any special restrictions on the above-mentioned electrical equipment.

[0191] Figure 7 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. Figure 7 As shown, the present application provides an electrical device, which is a vehicle.

[0192] The vehicle 1 can be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 40, a controller 30 and a lithium-ion secondary battery 10 can be arranged inside the vehicle 1, and the controller 30 is used to control the lithium-ion secondary battery 10 to power the motor 40. For example, a lithium-ion secondary battery 10 can be arranged at the bottom, front or rear of the vehicle 1. The lithium-ion secondary battery 10 can be used to power the vehicle 1. For example, the lithium-ion secondary battery 10 can be used as an operating power supply for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power demand during the start-up, navigation and operation of the vehicle 1. In another embodiment of the present application, the lithium-ion secondary battery 10 can not only be used as an operating power supply for the vehicle 1, but also as a driving power supply for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0193] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.

[0194] Figure 8 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. Figure 8 As shown, the present application provides an electric device, which is an energy storage device 7. The energy storage device 7 may include a plurality of lithium-ion secondary batteries 10. The energy storage device 7 may be applied to a power station to store and release electric energy.

[0195] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0196] [Examples and Comparative Examples]

[0197] Example 1

[0198] (1) Preparation of the first artificial graphite

[0199] The calcined needle coke is crushed and classified to obtain the first aggregate, the volatile matter of the calcined needle coke is ≤2%, and the sulfur content is ≤0.5%. The first aggregate is ground and sieved to obtain primary particles with a volume particle size distribution Dv50 satisfying 13μm to 18μm, and the primary particles are mixed with asphalt at a mass ratio of 100:2, and then subjected to high-temperature graphitization treatment at 3100°C to obtain the first artificial graphite. The volume particle size distribution Dv501 of the first artificial graphite satisfies 13μm≤Dv501≤18μm, and R1 satisfies 0 <R1≤0.14。

[0200] (2) Preparation of the Second Artificial Graphite

[0201] The needle-shaped green coke is crushed and graded to obtain a second aggregate, wherein the volatile matter of the needle-shaped green coke is ≤8%, and the sulfur content is ≤0.6%. The second aggregate is ground and sieved to obtain primary particles of a second artificial graphite whose volume particle size distribution Dv504 satisfies 7μm≤Dv504≤9μm; the primary particles of the second artificial graphite are mixed with asphalt in a mass ratio of 100:5 to obtain secondary particles of the second artificial graphite whose volume particle size distribution Dv503 satisfies 13μm≤Dv503≤18μm; the primary particles of the second artificial graphite and the secondary particles of the second artificial graphite are uniformly mixed in a mass ratio of 20:80 to obtain an intermediate material, the intermediate material is uniformly mixed with asphalt in a mass ratio of 100:2, and a high-temperature graphitization treatment is performed at 3100°C to obtain a second artificial graphite.

[0202] (3) Preparation of positive electrode sheet

[0203] The positive electrode active material lithium iron phosphate, the binder polyvinylidene fluoride (PVDF), and the conductive agent carbon black (Super P) are mixed evenly in a mass content ratio of 96:2:2, dissolved in a solvent N-methylpyrrolidone (NMP), and fully stirred and mixed to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0204] (4) Preparation of negative electrode sheet

[0205] The first artificial graphite, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are dissolved in deionized water in a mass ratio of 96.6:0.80:1.2:1.4, and the mixture is stirred and mixed to prepare a first negative electrode slurry. The first negative electrode slurry is coated on the negative electrode current collector to obtain a negative electrode sheet provided with a first negative electrode active material layer. A second negative electrode slurry is prepared by dissolving a second artificial graphite, a conductive carbon black (Super P), a thickener sodium carboxymethyl cellulose, and a binder styrene-butadiene rubber in deionized water in a mass ratio of 97.0:0.80:1.0:1.2, stirring and mixing them evenly, and coating the second negative electrode slurry on the first negative electrode active material layer to obtain a negative electrode sheet provided with the first negative electrode active material layer and the second negative electrode active material layer, the first negative electrode active material layer is located between the second negative electrode active material layer and the negative electrode current collector, the second negative electrode active material layer is closer to the outer surface of the negative electrode sheet than the first negative electrode active material layer, and based on the total mass of the negative electrode active material layer, the mass ratio of the first artificial graphite to the second artificial graphite is 50:50.

[0206] The R1 of the first artificial graphite is 0.08, the gram capacity is 358 mAh / g, and the powder compaction density under 50 KN is 1.89 g / cc. The R2 of the second artificial graphite is 0.16, the gram capacity is 354.5 mAh / g, and the powder compaction density under 50 KN is 1.81 g / cc.

[0207] (5) Isolation film

[0208] The isolation film includes a 7 μm polyethylene film, and both sides of the base film in the thickness direction are respectively provided with a 1 μm Al2O3 ceramic coating, and a dispersed PVDF coating is also provided on the surface of the Al2O3 ceramic coating, and the coating weight of the PVDF coating is 1.5 mg.

[0209] (6) Preparation of electrolyte

[0210] The electrolyte includes a solvent and an electrolyte salt. The solvent is ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. The electrolyte salt is LiPF6 and the concentration of the electrolyte salt is 1 mol / L.

[0211] (7) Preparation of secondary battery monomers

[0212] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is added. After packaging, standing, forming, aging and other processes, a secondary battery cell is obtained.

[0213] Example 2

[0214] Compared with Example 1, the temperature of the high-temperature graphitization treatment of the first artificial graphite is 3200°C; the parameters of the crusher are set differently during the crushing and grading process of the first aggregate and the second aggregate. Specific parameters are shown in Table 1.

[0215] Example 3

[0216] Compared with Example 1, in the preparation process of the first artificial graphite, the first aggregate is ground and sieved to obtain primary particles with a volume particle size distribution Dv50 satisfying 13μm to 18μm, and then high-temperature graphitization is performed at 3100°C. The primary particles are not mixed with asphalt (no asphalt is added); and the parameters of the crusher are set differently during the crushing and grading process of the first aggregate and the second aggregate. Specific parameters are shown in Table 1.

[0217] Example 4

[0218] Compared with Example 1, the parameters of the crusher are set differently during the crushing and classification of the first aggregate; the temperature of the high-temperature graphitization treatment of the second artificial graphite is 3200° C. Specific parameters are shown in Table 1.

[0219] Example 5

[0220] Compared with Example 1, the parameters of the crusher are set differently during the crushing and grading of the first aggregate; during the preparation of the second artificial graphite, the primary particles of the second artificial graphite and the secondary particles of the second artificial graphite are mixed uniformly at a mass ratio of 20:80 to obtain an intermediate material, which is then subjected to high-temperature graphitization treatment at 3100°C, and the intermediate material is not mixed with asphalt (no asphalt is added). Specific parameters are shown in Table 1.

[0221] Example 6

[0222] Compared with Example 1, the first aggregate is spheroidized. Specific parameters are shown in Table 1.

[0223] Example 7

[0224] Compared with Example 1, the first aggregate was not ground. Specific parameters are shown in Table 1.

[0225] Embodiment 8-9

[0226] Compared with Example 1, the mass ratio of primary particles to secondary particles in the second artificial graphite is different. Specific parameters are shown in Table 1.

[0227] Comparative Example 1

[0228] Compared with Example 1, in the preparation process of the first artificial graphite, the first aggregate is ground and sieved to obtain primary particles with a volume particle size distribution Dv50 of 13 μm to 18 μm, and the primary particles are directly subjected to high-temperature graphitization treatment at 3000°C without being mixed with asphalt. Specific parameters are shown in Table 1.

[0229] Comparative Example 2

[0230] Compared with Example 1, the negative electrode active material layer only has the first negative electrode active material layer. Specific parameters are shown in Table 1.

[0231] Comparative Example 3

[0232] Compared with Example 1, the negative electrode active material layer only includes the second negative electrode active material layer. Specific parameters are shown in Table 1.

[0233] The specific parameters of the negative electrode active materials in the embodiments and comparative examples are shown in Table 1, and the specific parameters of the first artificial graphite, the second artificial graphite and the negative electrode sheet in the embodiments and comparative examples are shown in Table 2. The compaction density of the negative electrode sheet in Table 2 is the compaction density of the negative electrode sheet after cold pressing and before formation.

[0234] Table 1 Specific parameters of negative electrode active materials of Examples and Comparative Examples

[0235]

[0236]

[0237] Table 2 Specific parameters of the embodiments and comparative examples

[0238]

[0239] Table 3 Test results of embodiments and comparative examples

[0240]

[0241]

[0242] In Table 1, R1 represents the I of the first artificial graphite D1 / I G1The lower the R1 value, the lower the surface defect degree of the first artificial graphite; S represents the specific surface area of ​​the first artificial graphite; Dv50 represents the volume particle size distribution; R2 represents the I D2 / I G2 The lower the R2 value is, the lower the surface defect degree of the second artificial graphite is. In Table 3, T is the charging time of the secondary battery cell.

[0243] Examples 1-9 and Comparative Examples 1-3 and their test results are described as follows:

[0244] As shown in Examples 1 to 5 and Comparative Example 1 in Table 1 and Table 3, in Comparative Example 1, the energy density of the secondary battery cell was 187.9 Wh / kg, and the capacity retention rate after storage at 60 °C for 120 D was only 87.6%. The energy densities in Examples 1 to 5 were 184.3 Wh / kg, 184.1 Wh / kg, 184.5 Wh / kg, 184.7 Wh / kg, and 188.1 Wh / kg respectively, and the capacity retention rates after storage at 60 °C for 120 D were 91.1%, 90.8%, 91.3%, 90.9%, and 91.4% respectively. By setting the first negative electrode active material layer to include first artificial graphite, the first artificial graphite includes primary particles, and the surface defect degree of the primary particles is relatively low, which is beneficial to reducing the surface defect degree of the first artificial graphite; the volume particle size distribution Dv501 of the first artificial graphite satisfies 13 μm ≤ Dv501 ≤ 18 μm. When Dv501 ≥ 13 μm, the volume particle size distribution Dv501 of the first artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the material crushing process, thereby being beneficial to improving the storage performance of the first negative electrode active material layer; when Dv501 ≤ 18 μm, the risk of reducing the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the first artificial graphite can be reduced, and the energy density of the first negative electrode active material layer can be improved; R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14, the first artificial graphite has good integrity and uniformity, and the surface defect degree is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the first negative electrode active material layer, thereby being beneficial to the lithium ion secondary battery to take into account high energy density and storage performance; by setting the second negative electrode active material layer to include second artificial graphite, the second artificial graphite includes secondary particles, and the isotropy of the secondary particles is relatively high, which can improve the ion transport efficiency of the second negative electrode active material layer, thereby being beneficial to improving the kinetic performance of the lithium ion secondary battery; the volume particle size distribution Dv502 of the second artificial graphite satisfies 10 μm ≤ Dv502 ≤ 15.5 μm. When Dv502 ≥ 10 μm, the volume particle size distribution Dv502 of the second artificial graphite is relatively large and the specific surface area is relatively small, which is beneficial to reducing the surface defects introduced during the crushing process, thereby being beneficial to improving the storage performance of the second negative electrode active material layer; when Dv502 ≤ 18 μm, the risk of reducing the compaction density and specific capacity of the negative electrode sheet caused by the too large particle size of the second artificial graphite can be reduced, and the energy density of the first negative electrode active material layer can be improved; R2 of the second artificial graphite satisfies 0.12 ≤ R2 ≤ 0.25, the surface defect degree of the second artificial graphite is relatively low, which is beneficial to reducing the consumption of active lithium and improving the storage performance of the second negative electrode active material layer; by providing the first negative electrode active material layer and the second negative electrode active material layer on the negative electrode current collector, pore structures in different directions are formed, increasing the ion transport path, which is further beneficial to improving the kinetic performance of the lithium ion secondary battery.

[0245] As shown in Examples 1-9 and Comparative Examples 2-3 in Tables 1 and 3, by providing a first negative electrode active material layer and a second negative electrode active material layer, pore structures in different directions can be formed, the ion transmission path is increased, and the charging time is less than 53.1 min in Comparative Example 2, while the energy density of the secondary battery cell and the capacity retention rate of storage at 60°C for 120D are both higher than 174.5Wh / kg and 86.4% in Comparative Example 3, which is beneficial for the lithium-ion secondary battery to have both high energy density, storage performance and kinetic performance.

[0246] As shown in Table 1 and Examples 1 and 6-7 in Table 3, the specific surface areas of the first artificial graphite in Examples 1 and 6-7 are 0.94 m 2 / g, 0.8m 2 / g, 1.5m 2 / g, the energy density is 184.3Wh / kg, 184.6Wh / kg, 187.6Wh / kg, and the capacity retention rate of 60℃ storage for 120D is 91.1%, 91.3%, 90.6%, because the specific surface area of ​​the first artificial graphite meets 0.8m 2 / g≤S≤1.5m 2 / g, a first artificial graphite with a smaller particle size can be obtained, and the gram capacity and compaction density of the first artificial graphite can be increased, which is beneficial to improving the energy density of the lithium-ion secondary battery, and at the same time is beneficial to reducing the side reaction between the first artificial graphite and the electrolyte, improving the storage performance of the lithium-ion secondary battery, and is beneficial to making the lithium-ion secondary battery have a balance of high energy density, storage performance and kinetic performance.

[0247] As shown in Examples 1-9 in Table 2, the gram capacity of the first artificial graphite is ≥356 mAh / g, and its compaction density is ≥1.75 g / cc; the gram capacity of the second artificial graphite is ≥353 mAh / g, and its compaction density is ≥1.70 g / cc; the gram capacity of the negative electrode plate is ≥357 mAh / g, and its compaction density is ≥1.67 g / cc. The use of the first artificial graphite with high compaction density and high gram capacity and the second artificial graphite can increase the gram capacity and compaction density of the negative electrode plate, which is beneficial to improving the energy density of the lithium-ion secondary battery; by setting the gram capacity of the first artificial graphite to be greater than or equal to the gram capacity of the second artificial graphite, the first negative electrode can be increased. The difference in gram capacity between the active material layer and the second negative electrode active material layer, by arranging the first artificial graphite on the side close to the negative electrode current collector, can make the first negative electrode active material layer have a high gram capacity, which is beneficial to improve the energy density of the lithium ion secondary battery body; by setting the powder compaction density of the second negative electrode active material to be smaller than the powder compaction density of the first negative electrode active material, the compression difference between the first negative electrode active material layer and the second negative electrode active material layer can be increased, so that ions can pass through the low-compression second negative electrode active material layer more smoothly, thereby improving the kinetic performance of the lithium ion secondary battery, which is beneficial to make the lithium ion secondary battery have a balance of high energy density, storage performance and kinetic performance.

[0248] As shown in Table 1 and Example 1 and Example 8-9 in Table 3, the mass ratio of the primary particles and the secondary particles of the second artificial graphite is 20:80, 30:70, and 10:90, respectively, and the energy density of the secondary battery monomer is 184.9Wh / kg and 184.6Wh / kg, respectively, and the capacity retention rate of 120D stored at 60°C is 91.1% and 91.7%, respectively. By controlling the mass ratio of the primary particles and the secondary particles of the second artificial graphite to meet the range of 30:70 to 10:90, the primary particles of the second artificial graphite can be filled on the surface of the secondary particles and in the gaps between the particles, reducing the phenomenon of accumulation between the particles due to excessive primary particles, which is beneficial to improving the energy density and storage performance of the lithium-ion secondary battery, thereby facilitating the lithium-ion secondary battery to take into account high energy density, storage performance and dynamic performance.

[0249] [Battery cell parameter test method]

[0250] (1) Test method for volume particle size distribution

[0251] As an example, the volume particle size distribution of artificial graphite can be determined by a particle size analyzer-laser diffraction method. Specifically, the standard GB / T19077-2016 can be referred to, and a laser diffraction scattering particle size analyzer can be used to measure according to the manufacturer's instructions. For example, before preparing the negative electrode sheet, take an appropriate amount of sample (secondary particles of the first artificial graphite, the second artificial graphite, and the primary particles of the second artificial graphite), and use Malvern 3000 (MasterSizer 3000) laser particle size analyzer to test the average volume particle size of the material. Take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8-12% shading), add 20ml of deionized water, and supercharge for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO13320:2009 standard.

[0252] As another example, the negative electrode sheet is cut in the thickness direction and placed under a scanning electron microscope (SEM) for observation. An area of ​​20 μm*20 μm is selected, the number of the first artificial graphite and the second artificial graphite particles and the particle size of the particles are counted, and a particle size distribution curve is drawn, and the particle size distribution of the first artificial graphite and the second artificial graphite is obtained according to the particle size distribution curve.

[0253] (2) Powder compaction density test

[0254] As an example, the compaction density of artificial graphite powder can be measured under a pressure of 50 KN using the UTM7305 compaction density analyzer produced by Sansi Zongheng Technology Co., Ltd.

[0255] Specifically, as an example, weigh 1g of sample (first artificial graphite, secondary particles, primary particles of second artificial graphite or negative electrode active material) and add it to a cylindrical mold, and the cross-sectional area of ​​the circular hole of the mold is S. Apply 50KN pressure to the powder in the mold, and maintain the pressure for 30s, and record the thickness of the powder as t. The compacted density of artificial graphite powder can be calculated by the following formula: ρ = m / (S×t), where ρ is the compacted density, m is the mass of artificial graphite, S is the cross-sectional area of ​​the circular hole of the mold, and t is the thickness of the powder.

[0256] (3) Test of compaction density of negative electrode

[0257] In the present application, the compaction density of the negative electrode plate can be tested using methods known in the art.

[0258] As an example, the following method can be used for testing: take a negative electrode sheet that is coated on one side and cold-pressed at 50KN (if it is a double-sided coated sheet, the negative electrode active material layer on one side can be wiped off first), or a negative electrode sheet disassembled from a secondary battery cell prepared by the above method (the negative electrode sheet disassembled from the secondary battery cell can be simply rinsed with DMC to remove residual electrolyte or reaction by-products on the surface and inside of the sheet), punch it into small discs with an area of ​​S1, weigh it, and record it as M1; test the thickness of the negative electrode active material layer, which is recorded as H; then wipe off the negative electrode active material layer, weigh the weight of the negative electrode collector, and record it as M2; the compaction density of the negative electrode sheet dc = (M1-M2) / S1 / H.

[0259] (4) Gram capacity test

[0260] A button cell was prepared using the negative electrode active material prepared above, and the button cell was tested. Specifically, the first artificial graphite, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were dissolved in deionized water at a mass ratio of 96.6:0.80:1.2:1.4, and the mixture was stirred and mixed to prepare a first negative electrode slurry, and the first negative electrode slurry was coated on the negative electrode current collector to obtain a negative electrode sheet provided with a first negative electrode active material layer. A second negative electrode slurry was prepared by dissolving a second artificial graphite, a conductive carbon black (Super P), a thickener sodium carboxymethyl cellulose, and a binder styrene-butadiene rubber in deionized water in a mass ratio of 97.0:0.80:1.0:1.2, and stirring and mixing them evenly. The second negative electrode slurry was coated on the first negative electrode active material layer to obtain a negative electrode sheet provided with the first negative electrode active material layer and the second negative electrode active material layer. A lithium sheet was used as a positive electrode sheet, and a polyethylene (PE) film was used as an isolation film to prepare a button half-cell. The button cell was placed in an oven at 25°C, left to stand for 2 hours, and then a charge and discharge test was performed.

[0261] As an example, according to the above steps, the first negative electrode slurry or the second negative electrode slurry can be coated on the negative electrode current collector to prepare a negative electrode sheet, and the gram capacity of the first artificial graphite and the second artificial graphite can be obtained respectively.

[0262] The charge and discharge process is as follows: charge to 0.005V with a constant current of 0.15mA, and pause for 5 minutes; discharge to 0.005V with a constant current of 10μA; then charge to 2.0V with a constant current of 0.3mA, and record the charging capacity of the button battery at this time, with the gram capacity of the button battery = charging capacity of the button battery / mass of the negative electrode active material.

[0263] (5) Test of energy density of secondary battery cells

[0264] A lithium-ion secondary battery cell is prepared by using the negative electrode active material, and the lithium-ion secondary battery cell is tested.

[0265] At 25°C, the lithium-ion secondary battery cell is charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V constant voltage, left to stand for 5 minutes, then discharged to 2.5V at 1 / 3C constant current, and the discharge energy of the lithium-ion secondary battery cell is recorded. The mass energy density of the lithium-ion secondary battery cell (Wh / kg) = the discharge energy of the lithium-ion secondary battery cell / the mass of the negative electrode active material in the lithium-ion secondary battery cell.

[0266] (6) Specific surface area test method

[0267] As an example, the specific surface area is tested by gas adsorption method according to the GB / T19587 2017 test standard.

[0268] The details are as follows: take the negative electrode active material as the sample, immerse the sample tube in liquid nitrogen at -196°C, measure the adsorption amount of nitrogen on the solid surface at different pressures at a relative pressure of 0.05-0.30, and obtain the monolayer adsorption amount of the sample based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area.

[0269] (7) Charging time test

[0270] A lithium-ion secondary battery monomer was prepared by using the negative electrode active material, and the lithium-ion secondary battery monomer was tested.

[0271] At 25°C, the lithium-ion secondary battery cell was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the lithium-ion secondary battery cell was discharged to 2.5C at a constant current of 0.33C, and its actual capacity C0 was recorded.

[0272] Then the lithium-ion secondary battery monomer is charged with 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C, constant current to 3.65V or 0V negative electrode cut-off potential (whichever is reached first), and after each charging is completed, it is necessary to discharge to 2.5V at 1C0, and record the state of charge at different charging rates to 10% SOC, 20% SOC, 30% SOC, 40% SOC, 50% SOC, 60% SOC, 70% SOC, 80% SOC (state of The charging rate-negative electrode potential curve under different SOC states is drawn, and the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained after linear fitting. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC respectively. According to the formula (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, the charging time T of the lithium ion secondary battery monomer from 10%SOC to 80%SOC (under the premise that the lithium ion secondary battery monomer does not precipitate lithium) is obtained, and the unit is min. The shorter the charging time is, the better the dynamic performance of the lithium-ion secondary battery cell is.

[0273] (8) Test of the capacity retention rate of secondary battery cells

[0274] At 60°C, the secondary battery cell was charged to 3.65V at a constant current of 1C, then charged at a constant voltage to a current of 0.05C and left to stand for 5 minutes; the secondary battery cell was discharged to 2.5V at a rate of 1C, and the discharge capacity was recorded as D0; the secondary battery cell was charged to 3.65V at a constant current of 1C, stored at 60°C for 120 days, and the discharge capacity was recorded as D1.

[0275] The capacity retention rate of the secondary battery cell (%) = D1 / D0×100%.

[0276] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: include: A negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer being located between the negative electrode current collector and the second negative electrode active material layer, Among them, the first negative electrode active material layer includes first artificial graphite, the first artificial graphite includes primary particles, and the volume particle size distribution Dv501 of the first artificial graphite satisfies: 13 μm ≤ Dv501 ≤ 18 μm; the R1 of the first artificial graphite satisfies: 0 < R1 ≤ 0.14; where, R = I D1 / I G1 , I D1 is the intensity of the D peak, which is the maximum peak intensity in the range of 1300 cm -1 -1400 cm -1 in the Raman spectrum of the first artificial graphite, and I G1 is the intensity of the G peak, which is the maximum peak intensity in the range of 1535 cm -1 -1635 cm -1 in the Raman spectrum of the first artificial graphite; The second negative electrode active material layer includes a second artificial graphite; the second artificial graphite includes secondary particles, and the volume particle size distribution Dv502 of the second artificial graphite satisfies: 10 μm≤Dv502≤15.5 μm; R2 of the second artificial graphite satisfies: 0.12≤R2≤0.25; Where R2 = I D2 / I G2 , I D2 The Raman spectrum of the second artificial graphite is 1300 cm -1 -1400cm -1 The maximum peak intensity within the range is the intensity of the D peak, I G2 The Raman spectrum of the second artificial graphite is 1535cm -1 -1635cm -1 The maximum peak intensity within the range is the intensity of the G peak.

2. The lithium ion secondary battery according to claim 1, characterized in that: 15μm≤Dv501≤16μm; and / or, 11≤Dv502≤13.5μm.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The specific surface area S1 of the first artificial graphite satisfies: 0.8 m 2 / g≤S≤1.5m 2 / g.

4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The disorder degree R2 of the second artificial graphite satisfies: R1 <R2≤0.25。 5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The gram capacity of the first artificial graphite is greater than or equal to the gram capacity of the second artificial graphite.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The gram capacity of the first artificial graphite is 356 mAh / g to 363 mAh / g; and / or, The gram capacity of the second artificial graphite is 353 mAh / g to 358 mAh / g.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The powder compaction density of the first artificial graphite under a pressure of 50 KN is greater than or equal to the powder compaction density of the second artificial graphite under a pressure of 50 KN.

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The powder compaction density of the first artificial graphite under a pressure of 50 KN is 1.75 g / cc to 1.94 g / cc; and / or the powder compaction density of the second artificial graphite under a pressure of 50 KN is 1.70 g / cc to 1.90 g / cc.

9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The second artificial graphite further includes primary particles, and based on the total mass of the second artificial graphite, a mass ratio of the primary particles of the second artificial graphite to the secondary particles of the second artificial graphite satisfies 30:70 to 10:

90.

10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that: The OI value of the first artificial graphite is greater than the OI value of the second artificial graphite; and / or, The OI value OI3 of the first artificial graphite material satisfies: OI2≤OI3≤11; and / or, The OI value OI1 of the secondary particles of the second artificial graphite satisfies: 2≤OI1≤5; and / or, The OI value OI2 of the primary particles of the second artificial graphite satisfies: 7≤OI2≤10.

11. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The second artificial graphite satisfies at least one of the following conditions: The volume particle size distribution Dv503 of the secondary particles of the second artificial graphite satisfies: 13 μm≤Dv503≤18 μm; The secondary particles of the second artificial graphite have a powder compaction density of 1.81 g / cc to 1.92 g / cc under a pressure of 50 KN; The gram capacity of the secondary particles of the second artificial graphite is 353.0 mAh / g to 358.2 mAh / g.

12. The lithium ion secondary battery according to any one of claims 1 to 11, characterized in that: The second artificial graphite satisfies at least one of the following conditions: The volume particle size distribution Dv504 of the primary particles of the second artificial graphite satisfies: 7 μm≤Dv504≤9 μm; The volume particle size distribution Dv1 of the primary particles of the second artificial graphite satisfies: Dv1>3 μm; The primary particles of the second artificial graphite have a powder compaction density of 1.78 g / cc to 1.80 g / cc under a pressure of 50 kN; The gram capacity of the primary particles of the second artificial graphite is 354.1 mAh / g to 358.6 mAh / g.

13. The lithium ion secondary battery according to any one of claims 1 to 12, characterized in that: The negative electrode plate meets at least one of the following conditions: The compaction density of the negative electrode sheet at 50KN is 1.67g / cc to 1.75g / cc; The gram capacity of the negative electrode plate is 357 mAh / g to 360 mAh / g; The surface density of the negative electrode plate is 5.0 mg / cm 2 ~25.0mg / cm 2 ; The thickness d of the negative electrode plate satisfies: 70 μm≤d≤250 μm.

14. A method for preparing a lithium ion secondary battery, characterized in that: include: crushing and classifying the calcined needle coke to obtain a first aggregate, and performing surface shaping treatment on the first aggregate to obtain primary particles; The primary particles are subjected to high temperature graphitization to obtain a first artificial graphite, wherein the volume particle size distribution Dv501 of the first artificial graphite satisfies: 13 μm ≤ Dv501 ≤ 18 μm, and R1 of the first artificial graphite satisfies: 0 <R1≤0.14; Where R = I D1 / I G1 , I D1 The Raman spectrum of the first artificial graphite is 1300 cm -1 ~1400cm -1 The maximum peak intensity in the range is the intensity of the D peak, and IG1 is the peak at 1535 cm in the Raman spectrum of the first artificial graphite. -1 ~1635cm -1 The maximum peak intensity within the range is the intensity of the G peak; The needle-shaped green coke is crushed and classified to obtain a second aggregate, the second aggregate is subjected to surface shaping treatment, and mixed with a binder to form a granule to obtain an intermediate material including secondary particles; The intermediate material is subjected to high temperature graphitization treatment to obtain a second artificial graphite, wherein the volume particle size distribution Dv502 of the second artificial graphite satisfies: 10 μm≤Dv502≤15.5 μm; and R2 of the second artificial graphite satisfies: 0.12≤R2≤0.25; Where R2 = I D2 / I G2 , I D2 The Raman spectrum of the second artificial graphite is 1300 cm -1 -1400cm -1 The maximum peak intensity within the range is the intensity of the D peak, I G2 The Raman spectrum of the second artificial graphite is 1535cm -1 -1635cm -1 The maximum peak intensity within the range is the intensity of the G peak; Using the first artificial graphite to prepare a first negative electrode slurry, coating the first negative electrode slurry on at least one side of the negative electrode current collector to prepare a first negative electrode active material layer; Using the second artificial graphite to prepare a second negative electrode slurry, coating the second negative electrode slurry on the surface of the first negative electrode active material layer to prepare a negative electrode sheet provided with a second negative electrode active material layer; A positive electrode plate, the negative electrode plate and a separator are provided to assemble into an electrode assembly, the electrode assembly is placed in an outer package for packaging, and an electrolyte is injected and packaged to obtain a lithium-ion secondary battery.

15. The preparation method according to claim 14, characterized in that: The volatile matter of the calcined needle coke is ≤2%, and the sulfur content is ≤0.5%; and / or, The volatile matter of the needle-shaped green coke is ≤8%, and the sulfur content is ≤0.6%.

16. The preparation method according to claim 14 or 15, characterized in that: The surface shaping treatment includes at least one of grinding, screening, spheroidization and coating treatment.

17. The preparation method according to any one of claims 14 to 16, characterized in that: The processing temperature of the high temperature graphitization is greater than or equal to 3000°C.

18. The preparation method according to any one of claims 14 to 17, characterized in that: The intermediate material further includes primary particles obtained by performing surface shaping treatment on the second aggregate, and based on the total mass of the intermediate material, a mass ratio of the primary particles to the secondary particles satisfies 30:70 to 10:

90.

19. An electrical device, characterized in that: include: The lithium ion secondary battery according to any one of claims 1 to 13; And / or, the lithium ion secondary battery obtained by the preparation method according to any one of claims 14-18, wherein the lithium ions are secondary used to provide electrical energy to the electrical device.

Citation Information

Patent Citations

  • Negative electrode piece, preparation method thereof and lithium ion battery

    CN114005957A

  • Battery monomer, battery and electric device

    CN117976818A

  • Secondary battery, apparatus, artificial graphite and preparation method thereof

    US20210313575A1

  • Secondary battery and electric apparatus

    US20230231134A1

Cited By

  • High-performance double-layer graphite negative electrode and preparation method and application thereof

    CN120690811A

  • Negative plate, battery, battery pack and electric device

    CN121355187A

  • Lithium-ion secondary battery and manufacturing method therefor, and electrical apparatus

    WO2026170778A1